At low T g Enhanced directed self-assembly in the presence of oligomers for patterning

By coating and thermally annealing the neutral layer using a block copolymer composition of a low Tg oligomer material, the problems of defects resulting from limited resolution capabilities of photolithography and excessive thickness of block copolymer film in the prior art are solved, and higher pattern resolution and density are achieved.

CN113286833BActive Publication Date: 2025-03-07MERCK PATENT GMBH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080008010.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2020-01-15
Publication Date
2025-03-07
Estimated Expiration
2040-01-15

AI Technical Summary

Technical Problem

The prior art When manufacturing microelectronic devices, the resolution ability of the photolithography technology is limited, making it difficult to further reduce the pattern size. When the thickness of the block copolymer film exceeds 50 nm, defects are prone to occur, such as dislocation, bridging and collapse.

Method used

Using a novel block copolymer composition containing low Tg oligomer materials, the self-assembly is affected by coating on the neutral layer and thermal annealing, the number of defects is reduced and the pattern is transferred during plasma etching.

Benefits of technology

It effectively reduces the number of defects in the block copolymer domain under high film thickness, improves pattern resolution and density, and enhances the resolution ability of traditional lithography technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113286833B_ABST
    Figure CN113286833B_ABST
Patent Text Reader

Abstract

The present invention relates to a composition comprising components a), b) and c). Component a) is a block copolymer or a blend of block copolymers. Component b) is a low T copolymer selected from the group consisting of an oligomeric random copolymer b-1), an oligomeric diblock copolymer b-2), an oligomeric diblock copolymer b-3) and a mixture of at least two of these. g The invention further relates to a novel oligomeric diblock copolymer b-2), which is an oligomeric diblock copolymer of block A-b) and block B-b), wherein block A-b) is a random copolymer of repeating units of structures (III) and (IV), and block B-b) is a random copolymer of repeating units of structures (V) and (VI).
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to block copolymers and block copolymer compositions and novel methods for using the block copolymer compositions to arrange microdomains of self-assembled block copolymers (BCPs) to form self-assembled geometric structures for forming contact holes or line and space arrays. These compositions and methods can be used to manufacture electronic devices.

[0002] background

[0003] Self-assembly of block copolymers is a method for producing smaller and smaller patterned features for manufacturing microelectronic devices, wherein nanometer-scale critical dimensions (CD) of features can be achieved. Self-assembly methods are needed to expand the resolution capabilities of microlithography for repeating features such as contact hole arrays or pillar arrays. In conventional photolithography methods, ultraviolet (UV) radiation can be used to expose to a photoresist layer coated on a substrate or layered substrate through a mask. Positive or negative photoresists are useful, and they can also contain refractory elements, such as silicon, to use conventional integrated circuit (IC) plasma processes for dry development. In positive photoresists, UV radiation transmitted through the mask causes a photochemical reaction in the photoresist, causing the exposed area to be removed with a developer solution or by a conventional IC plasma process. In contrast, in negative photoresists, UV radiation transmitted through the mask causes the area exposed to the radiation to become difficult to remove with a developer solution or by a conventional IC plasma process. Integrated circuit features such as gates, vias, or interconnects are then etched into the substrate or layered substrate, and the remaining photoresist is removed. When using conventional photolithography exposure processes, the feature size of integrated circuit features is limited. Radiation exposure is difficult to achieve further reductions in pattern size due to limitations associated with aberrations, focusing, proximity effects, minimum achievable exposure wavelength, and maximum achievable numerical aperture. The demand for large-scale integration has led to a continuous reduction in circuit size and features in devices. In the past, the ultimate resolution of features depended on the wavelength of light used to expose the photoresist, which has its own limitations. Directed (aka guided) self-assembly techniques using patterned areas on a substrate, such as graphoepitaxy and chemical epitaxy using block copolymer imaging, are highly desirable techniques for improving resolution while reducing CD variation. These techniques can be used to enhance conventional UV lithography techniques, or to achieve higher resolution and CD control in methods using EUV, electron beam, deep UV, or immersion lithography. Directed self-assembling block copolymers contain blocks of etch-resistant copolymer units and blocks of highly etchable copolymer units, which, when coated, arranged, and etched on a substrate, produce areas of very high density patterns.

[0004] For the directional (guiding) or non-guided self-assembly of the block copolymer film on the patterned or non-patterned substrate area respectively, the self-assembly process of the block polymer layer usually occurs during the annealing of the film covering the neutral layer. The neutral layer on the semiconductor substrate can be an unpatterned neutral layer, or in chemical epitaxy or graphoepitaxy, the neutral layer can respectively include graphoepitaxy or chemical epitaxy guiding features (formed by the above-mentioned UV lithography). In the annealing process of the block copolymer film, the following neutral layer guides the nanophase separation of the block copolymer domain. An example is to form a phase-separated domain, which is a thin sheet or cylinder perpendicular to the neutral layer surface below. The block copolymer domains of these nanophase separations form a pre-pattern (such as line and space L / S) that can be transferred to the substrate by an etching process (such as plasma etching). In graphoepitaxy or chemical epitaxy, these guiding features can indicate pattern correction and pattern multiplication. In the case of an unpatterned neutral layer, this will produce a repeating array such as L / S or CH. For example, in conventional block copolymers such as poly(styrene-b-methyl methacrylate) (P(Sb-MMA)), where the two blocks have similar surface energies at the BCP-air interface, this can be achieved by coating and thermally annealing the block copolymer on a layer of non-preferential or neutral material grafted or cross-linked at the polymer-substrate interface.

[0005] In the graphene epitaxy directed self-assembly method, block copolymers are self-organized around a substrate pre-patterned with conventional photolithography (ultraviolet light, deep UV, electron beam, extreme UV (EUV) exposure source) to form repeated morphological features such as line / space (L / S) or contact hole (CH) patterns. In an example of L / S directed self-assembly arrays, block copolymers can form self-arranged layered regions that can form parallel line-space patterns of different spacings in the grooves between pre-patterned lines, thereby enhancing pattern resolution by subdividing the groove spacing between the morphological lines into finer patterns. For example, diblock copolymers or triblock copolymers of carbon-rich blocks (such as styrene or some other elements such as Si, Ge, Ti) and highly plasma-etchable or removable blocks that can be microphase separated and resist plasma etching can be provided with high-resolution pattern accuracy. Examples of highly etchable blocks can include monomers rich in oxygen and free of refractory elements and capable of forming highly etchable blocks, such as methyl methacrylate. The plasma etching gases used in the etching process that defines the self-assembled pattern are typically those used in the process for manufacturing integrated circuits (ICs). In this way, finer patterns can be created in a typical IC substrate than can be defined by conventional photolithography, thereby achieving pattern multiplication. Similarly, features such as contact holes can be made denser by using graphoepitaxy, in which suitable block copolymers arrange themselves around an array of contact holes or an array of pillars defined by conventional photolithography through directed self-assembly, thereby forming a denser array of etchable areas and etch-resistant domains, which will produce a denser array of contact holes when etching. Therefore, graphoepitaxy has the potential to provide pattern correction and pattern multiplication.

[0006] In chemical epitaxy or pinning chemical epitaxy, the self-assembly of block copolymers is formed on a surface, and the guiding feature of the surface is a region with different chemical affinities, which does not have or has no significant morphology (also known as non-guided morphology) that indicates a directed self-assembly process. For example, conventional photolithography (UV, deep UV, electron beam EUV) can be used to pattern the substrate surface to create a surface with different chemical affinities in a line and space (L / S) pattern, wherein the surface chemistry of the exposed area has been changed by irradiation, alternating with an unexposed area that does not show a chemical change. There are no morphological differences in these areas, but there are indeed surface chemical differences or pinning to direct the self-assembly of the block copolymer segments. Specifically, the directed self-assembly of block copolymers containing etching resistance (such as styrene repeating units) and fast etching repeating units (such as methyl methacrylate repeating units) will allow the accurate placement of etching resistance block segments and highly etchable block segments on the pattern. This technology allows the precise placement of these block copolymers and the subsequent pattern transfer from the pattern to the substrate after plasma or wet etching treatment. The advantage of chemical epitaxy is that it can be fine-tuned through changes in chemical differentiation to help improve line-edge roughness and CD control, allowing pattern correction. Other types of patterns, such as repeating contact hole (CH) arrays, can also be pattern corrected using chemical epitaxy.

[0007] These neutral layers are layers on the surface of the substrate or treated substrate that have no affinity for any of the block segments of the block copolymer for directed self-assembly. In the graphoepitaxy method for directed self-assembly of block copolymers, neutral layers are useful because they allow the block polymer segments for directed self-assembly to be correctly placed or oriented, which results in the correct placement of etch-resistant block polymer segments and highly etchable block polymer segments relative to the substrate. For example, in a surface containing line and space features defined by conventional radiation lithography, the neutral layer allows the block segments to be oriented so that the block segments are oriented perpendicular to the substrate surface, depending on the length of the block segments in the block copolymer, which is related to the length between the lines associated with conventional lithography, and this orientation is ideal for both pattern correction and pattern multiplication. If the interaction of the substrate with one of the block segments is too strong, it will cause it to lie flat on the surface to maximize the contact surface between the segment and the substrate; such a surface will disrupt the vertical alignment required for pattern correction or pattern multiplication based on features created by conventional lithography. Modification or pinning of selected small regions of the substrate so that they interact strongly with one block of the block copolymer and the remaining surface is coated with a neutral layer can be used to force the block copolymer domains to orient in a desired direction, which is the basis for pinned chemical epitaxy or graphoepitaxy for pattern multiplication.

[0008] Although self-assembly using polystyrene-b-polymethylmethacrylate (PS-b-PMMA) is widely used as a next-generation patterning material in lithography, the nanophase separation assembly process produces well-aligned domain arrays, but this is accompanied by the formation of a large number of defects if the film thickness exceeds 50nm. These defects are significant in contact holes and line / space multiplication processes and need to be significantly reduced to improve device yields in any commercially viable IC manufacturing using directed self-assembly. One of the root causes of defects is insufficient diffusion of block chain segments, which can produce defects such as dislocations, bridging, networks, and line or cylinder collapse. Therefore, new materials and processes are needed that can affect directed self-assembly even in such thick films. We have found many low T g Oligomer materials, which can be used as additives in the formation of novel block copolymer compositions, can affect the self-assembly of block copolymer domains, greatly reducing the number of these defects even at film thicknesses exceeding 50 nm.

[0009] Detailed Description of the Drawings

[0010] Figure 1 Top-down SEM contact hole array study of self-assembled films of block copolymers of styrene and methyl methacrylate with and without oligomeric (S-co-MMA) additives [Synthesis Example 5]: Film thickness 50 nm (~1 L o ); the film is cast on the neutral layer film. The neutral layer is formed by casting neutral formulation example 1 (74% PS) on a silicon wafer and baking at 240°C / 5min, then rinsing with PGMEA for 30 seconds and baking at 110°C for 1min. Films of formulations 1 to 3 (formulation examples 1 to 3) containing 1.5wt% solids in PGMEA and a blend of P(Sb-MMA) and 0 to 20wt% of oligomeric (S-co-MMA) in PGMEA (listed in Table 1) are spun on top of the neutral layer at a speed of 1500rpm to form a film (Lo=45.3 / FT 50nm), then baked at 250°C under nitrogen for 5min to affect self-assembly and etched with oxygen plasma for 50 and 70 seconds.

[0011] Figure 2 X-section SEM contact hole array study of self-assembled films of block copolymers of styrene and methyl methacrylate with and without oligomeric (S-co-MMA) additives [Synthesis Example 5]: Film thickness 50 nm (~1 L o); the film is cast on the neutral layer film. The neutral layer is formed by casting neutral formulation example 1 (74% PS) on a silicon wafer and baking at 240°C / 5min, then rinsing with PGMEA for 30 seconds and baking at 110°C for 1min. Films of formulations 2 and 3 (formulation examples 2 and 3) containing 1.5wt% solids in PGMEA and a blend of P(Sb-MMA) and 10 to 20wt% of oligomeric (S-co-MMA) in PGMEA (listed in Table 1) (listed in Table 1) are spun on top of the neutral layer at a speed of 1500rpm to form a film (Lo=45.3 / FT 50nm), then baked at 250°C under nitrogen for 5min to affect self-assembly and etched with oxygen plasma for 50 seconds.

[0012] Figure 3 Top-down SEM contact hole study of self-assembled films of block copolymers of styrene and methyl methacrylate with and without oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) additives [Synthesis Example 8]: Film thickness 50 nm (~1 L o ); cast on the neutral layer film. The neutral layer was formed by casting neutral Formulation Example 1 (74% PS) on a silicon wafer and baking at 240°C / 5min, then rinsing with PGMEA for 30 seconds and baking at 110°C for 1min. Films of Formulations 1, 4 and 5 (Formulation Examples 1, 4 and 5) containing 1.5wt% solids in PGMEA and a blend of P(Sb-MMA) and 0 to 20wt% of oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) (Synthesis Example 8) in PGMEA (listed in Table 1) were spun on top of the neutral layer at a speed of 1500rpm to form a film (Lo=45.3 / FT 50nm), then baked at 250°C under nitrogen for 5min to affect self-assembly, and then etched with oxygen plasma for 50 and 70 seconds.

[0013] Figure 4 Top-down SEM line and space studies of self-assembled films of block copolymers of styrene and methyl methacrylate with and without oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) additives [Synthesis Example 9]: Film thickness 50 nm (~1 L o); the film is cast on the neutral layer film. The neutral layer is formed by casting neutral formulation example 1 (74% PS) on a silicon wafer and baking at 240°C / 5min, then rinsing with PGMEA for 30 seconds and baking at 110°C for 1min. Films of formulations 6, 10, 11 and 12 (formulation examples 6, 10, 11 and 12) containing 1.5wt% solids in PGMEA and a blend of P(Sb-MMA) and 0 to 20wt% of oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) (Synthesis Example 9) in PGMEA (listed in Table 3) are spun on top of the neutral layer at a speed of 1500rpm to form a film (Lo=45.3 / FT 50nm), then baked at 250°C under nitrogen for 5min to affect self-assembly, and then etched with oxygen plasma for 50 and 70 seconds.

[0014] Figure 5 Top-down SEM L / S study of self-assembled films of block copolymers of styrene and methyl methacrylate with and without oligo(Sb-MMA) [Synthesis Example 8]: Film thickness 50 nm (~1 L o ); cast on the neutral layer film after etching with oxygen plasma. The neutral layer was formed by casting the neutral formulation example 1 (74% PS) on a silicon wafer and baking at 240°C / 5min, then rinsing with PGMEA for 30 seconds and baking at 110°C for 1min. Films of formulations 6 (0wt%), 13 (10wt%) and 14 (20wt%) (formulation examples 6, 13 and 14) containing 1.5wt% solids in PGMEA, block copolymer P(Sb-MMA) P(Sb-MMA) (42K-47K) and 0 to 20wt% of oligomeric (Sb-MMA) (Synthesis Example 7) in PGMEA (listed in Table 3) were spun on top of the neutral layer at a speed of 1500rpm to form a film (Lo=45.3 / FT 50nm), then baked at 250°C under nitrogen for 5min to affect self-assembly, and then etched with oxygen plasma for 30 seconds.

[0015] Figure 6 Top-down SEM L / S studies of self-assembled films of triblock copolymer Comparative Formulation 4 [Synthesis Example 4a (50K-88k-50k)] without oligomer, Formulation Example 15 with 20 wt% oligomer of Synthesis Example 9 or with 20 wt% oligomer of Synthesis Example 7a. SUMMARY OF THE INVENTION

[0017] One aspect of the present invention relates to a composition comprising components a), b) and c), wherein a) is a block copolymer component or a blend of at least two block copolymers, and b) is a low T copolymer selected from the group consisting of an oligomeric random copolymer b-1), an oligomeric diblock copolymer b-2), an oligomeric diblock copolymer b-3) and mixtures thereof. g Additives, wherein b-1), b-2) and b-3) are as follows, and c) is a spin casting solvent:

[0018] b-1) is an oligomeric random copolymer having two repeating units of structure (Ib) and structure (IIb), wherein R 1b and R 3b are independently selected from H or C-1 to C-4 alkyl, R 2b is H or C-1 to C-8 alkyl, R 4b is a C-1 to C-8 alkyl group, and based on the total moles of repeating units of structures (Ib) and (IIb), the mole % value of repeating units of structure (Ib) is from about 40 mole % to about 80 mole %, and the mole % value of repeating units of structure (IIb) is from about 20 mole % to about 60 mole %, and the respective values ​​of the mole % of repeating units of structures (Ib) and (IIb) are selected from their respective ranges so that the total moles of repeating units of structures (Ib) and (IIb) add up to 100 mole %; further, the T of the oligomeric random copolymer b-1) is g From about 0°C to about 80°C, M n From about 1000 g / mol to about 8000 g / mol, and a polydispersity of from about 1.3 to about 1.8,

[0019]

[0020] b-2) is an oligomeric diblock copolymer of block Ab) and block Bb), M n The molecular weight of the present invention is about 1,000 to 35,000 and the polydispersity is 1.0 to about 1.1, wherein block Ab) is a random copolymer having repeating units of structures (III) and (IV), block Bb) is a random copolymer having repeating units of structures (V) and (VI), and R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, R6 is C-7 to C-10 straight chain alkyl, R8 is C-1 to C-4 alkyl, R 10 is a C-1 to C-4 alkyl group, R 12 and R 13 are independently selected from C-2 to C-5 alkylene, and R 14 is a C-1 to C-4 alkyl group, and the oligomeric diblock copolymer b-2) has a T g Values ​​are from about 0°C to about 95°C.

[0021]

[0022] b-3) oligomeric diblock copolymers of blocks Ac) having repeating units of structure (Ic) and blocks Bc) having repeating units of structure (IIc), wherein R 1c and R 3c are independently selected from H or C-1 to C-4 alkyl, R 2c is H or C-1 to C-8 alkyl, R 4c is a C-1 to C-8 alkyl group, and based on the total moles of repeating units of structures (Ic) and (IIc), the mole % value of repeating units of structure (Ic) is from about 36 mole % to about 74 mole % and the mole % value of repeating units of structure (IIc) is from about 26 mole % to about 64 mole %, and the respective values ​​of the mole % of repeating units of structures (Ic) and (IIc) are selected from their respective ranges so that the total moles of repeating units of structures (Ic) and (IIc) add up to 100 mole %; and the M of the oligomeric diblock copolymer b-2) n is from about 1000 g / mol to about 30000 g / mol, has a polydispersity of from about 1.0 to about 1.1 and T g From about 0°C to about 115°C.

[0023]

[0024] Another aspect of the present invention is a method of using the above composition in a self-assembly process followed by pattern transfer of the self-assembled pattern into a substrate.

[0025] Another aspect of the invention is the novel oligomeric diblock copolymers b-2) as described above having blocks Ab) and blocks Bb). DETAILED DESCRIPTION OF THE INVENTION

[0027] It should be understood that the foregoing general description and the following detailed description are illustrative and explanatory, rather than limiting the subject matter claimed. In this application, unless otherwise specifically stated, the use of the singular includes the plural, the word "a" or "an" means "at least one", and the use of "or" means "and / or". In addition, the use of the term "include" and other forms such as "include" and "contain" is not restrictive. Similarly, unless otherwise specifically stated, terms such as "element" or "component" cover both elements and components containing one unit and elements or components containing more than one unit. As used herein, unless otherwise stated, the conjunction "and" is intended to be inclusive, while the conjunction "or" is not intended to be exclusive. For example, the phrase "or, alternatively" is intended to be exclusive. As used herein, the term "and / or" refers to any combination of the aforementioned elements, including the use of a single element.

[0028] The term C-1 to C-4 alkyl includes methyl and C-2 to C-4 straight chain alkyl and C-3 to C-4 branched chain alkyl moieties, for example, as follows: methyl (-CH3), ethyl (-CH2-CH3), n-propyl (-CH2-CH2-CH3), isopropyl (-CH(CH3)2, n-butyl (-CH2-CH2-CH2-CH3), tert-butyl (-C(CH3)3), isobutyl (CH2-CH(CH3)2, 2-butyl (-CH(CH3)CH2-CH3). Similarly, the term C-1 to C-8 includes methyl, C-2 to C-8 straight chain, C-3 to C-8 branched chain alkyl, C-4 to C-8 cycloalkyl (e.g., cyclopentyl, cyclohexyl, etc.) or C-5-C-8 alkylene cycloalkyl (e.g., -CH2-cyclohexyl, -CH2-CH2-cyclopentyl, etc.).

[0029] The term C-2 to C-5 alkylene includes C-2 to C-5 straight chain alkylene moieties (e.g., ethylene, propylene, etc.) and C-3 to C-5 branched chain alkylene moieties (e.g., -CH(CH3)-, -CH(CH3)-CH2-, etc.).

[0030] Diblock and triblock copolymers of styrene and acrylic acid moieties useful as components in the inventive compositions described herein can be prepared by a variety of methods, such as anionic polymerization, atom transfer radical polymerization (ATRP), reversible addition fragmentation chain transfer (RAFT) polymerization, living radical polymerization, etc. (Macromolecules 2019, 52, 2987-2994; Macromol. Rapid Commun. 2018, 39, 1800479; A. Deiter Shluter et al Synthesis of Polymers, 2014, Volume 1, p315; Encyclopedia of Polymer Science and Technology, 2014, Vol 7, p 625)

[0031] The random copolymer poly(styrene-co-methyl methacrylate) is abbreviated as "P(S-co-MMA)", and the oligomeric form of this material is abbreviated as oligo(S-co-MMA). Similarly, the block copolymer poly(styrene-block-methyl methacrylate) is abbreviated as P(Sb-MMA), and the oligomer of this material is abbreviated as oligo(Sb-MMA). The oligomer oligo(styrene-co-p-octylstyrene)-block-(methyl methacrylate-co-di(ethylene glycol)methyl ether methacrylate) uses the same abbreviation to represent the random and block copolymer elements, specifically, oligo(S-co-p-OS)-bP(MMA-co-DEGMEMA), where S = styrene, p-OS = p-octylstyrene, MMA = methacrylate, DEGMEMA = di(ethylene glycol)methyl ether methacrylate, indicating that two blocks are repeating units in this block copolymer of the random copolymer.

[0032] The term "g / mol" is an abbreviation for grams per mole.

[0033] FOV is the abbreviation for the field of view of a top-down scanning electron micrograph (SEM) of the SEM image. In the present applications 1, 3, 4 and 5, the field of view is 2 μm in this case. Figure 2 The cross-sectional electron micrograph (X-SEM) shown is at a magnification of 250 K. Field of view. The term "CH" is an abbreviation for contact hole lithographic feature, and the term "L / S" is an abbreviation for line and space lithographic feature.

[0034] In the following description, the term "synthesis" is an abbreviation of synthesis; the term "comparison" is an abbreviation of comparison; and the term "example" is an abbreviation of example.

[0035] As used herein, the terms oligomer, oligomeric and oligomeric polymer refer to low T gAdditive does not refer to low molecular weight polymers having molecular weight ranges specific to the type of additive indicated herein.

[0036] As used herein, the term acrylic acid includes repeating units derived from acrylate derivatives, typically, for example, repeating units derived from acrylate derivatives having the following structure, wherein the Alkyl moiety may be a C-1 to C-8 alkyl group, and Xacryl is H or a C-1 to C-4 alkyl group:

[0037]

[0038] As used herein, the term styrene includes repeating units derived from styrene derivatives, typically, for example, repeating units derived from styrene derivatives having the following structure, wherein the Xsty moiety is H or a C-1 to C-4 alkyl group and the Rsty moiety is H or a C-1 to C-8 moiety:

[0039]

[0040] One aspect of the present invention relates to a composition of the present invention comprising components a), b) and c), wherein a) is a block copolymer component or a blend of at least two block copolymers, b) is a low T copolymer selected from the group consisting of oligomeric random copolymers b-1), oligomeric diblock copolymers b-2), oligomeric diblock copolymers b-3) and mixtures thereof. g Additives, wherein b-1, b-2 and b-3 are as follows, and c) is a spin casting solvent:

[0041] b-1) is an oligomeric random copolymer having two repeating units of structure (Ib) and structure (IIb), wherein R 1b and R 3b are independently selected from H or C-1 to C-4 alkyl, R 2b is H or C-1 to C-8 alkyl, R 4b is a C-1 to C-8 alkyl group, and based on the total moles of repeating units of structures (Ib) and (IIb), the mole % value of repeating units of structure (Ib) is from about 40 mole % to about 80 mole %, and the mole % value of repeating units of structure (IIb) is from about 20 mole % to about 60 mole %, and the respective values ​​of the mole % of repeating units of structures (Ib) and (IIb) are selected from their respective ranges so that the total moles of repeating units of structures (Ib) and (IIb) add up to 100 mole %; further, the T of the oligomeric random copolymer b-1) is g From about 0°C to about 80°C, M n From about 1000 g / mol to about 8000 g / mol, and a polydispersity of from about 1.3 to about 1.8,

[0042]

[0043] b-2) is an oligomeric diblock copolymer of block Ab) and block Bb), M n The molecular weight of the present invention is about 1,000 to 35,000 and the polydispersity is 1.0 to about 1.1, wherein block Ab) is a random copolymer having repeating units of structures (III) and (IV), block Bb) is a random copolymer having repeating units of structures (V) and (VI), and R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, R6 is C-7 to C-10 straight chain alkyl, R8 is C-1 to C-4 alkyl, R 10 is a C-1 to C-4 alkyl group, R 12 and R 13 are independently selected from C-2 to C-5 alkylene, and R 14 is a C-1 to C-4 alkyl group, and the oligomeric diblock copolymer b-2) has a T g Values ​​are from about 0°C to about 95°C.

[0044]

[0045]

[0046] b-3) oligomeric diblock copolymers of blocks Ac) having repeating units of structure (Ic) and blocks Bc) having repeating units of structure (IIc), wherein R 1c and R 3c are independently selected from H or C-1 to C-4 alkyl, R 2c is H or C-1 to C-8 alkyl, R 4c is a C-1 to C-8 alkyl group. And based on the total moles of repeating units of structures (Ic) and (IIc), the mole % value of repeating units of structure (Ic) is from about 36 mole % to about 74 mole % and the mole % value of repeating units of structure (IIc) is from about 26 mole % to about 64 mole %, and the respective values ​​of the mole % of repeating units of structures (Ic) and (IIc) are selected from their respective ranges so that the total moles of repeating units of structures (Ic) and (IIc) add up to 100 mole %; and the M of the oligomeric diblock copolymer b-2) n is from about 1000 g / mol to about 30000 g / mol, has a polydispersity of from about 1.0 to about 1.1 and T g From about 0°C to about 115°C.

[0047]

[0048] Another aspect of the inventive composition described herein comprising components a), b) and c) is an embodiment wherein component a) is selected from a single triblock copolymer and a blend of at least two triblock copolymers, or a single diblock copolymer and a blend of at least two diblock copolymers.

[0049] Component a) is a triblock copolymer

[0050] Another aspect of the described composition of the present invention comprising components a), b) and c) is an embodiment wherein the component a) is an ABA triblock copolymer component selected from the group consisting of ABA triblock copolymers a-1t), ABA triblock copolymers a-2t), and blends of ABA triblock polymers a-1t) and ABA triblock copolymers a-2t).

[0051] In the above embodiment, a-1t) is an ABA triblock copolymer comprising a middle B styrene block segment having a repeating unit of styrene structure (I) and two terminal acrylic block A) segments of equal length having structure (II), wherein R1 and R3 are independently selected from H and C-1 to C-4 alkyl, R2 is H or C-1 to C-8 alkyl, and R4 is C-1 to C-8 alkyl. In addition, in this embodiment, based on the total moles of repeating units of structures (I) and (II), the mole % value of repeating units of structure (I) is from about 40 mole % to about 80 mole %, and the mole % value of repeating units of structure (II) is from about 20 mole % to about 60 mole %, wherein the respective values ​​of the mole % of repeating units of structures (I) and (II) are selected from their respective ranges so that the total moles of repeating units of structures (I) and (II) add up to 100 mole %, and the polydispersity of the triblock copolymer a-1t) is from about 1.0 to about 1.1, and M n From about 70,000 g / mol to about 350,000 g / mol. In one aspect of this embodiment, the moiety R2 is attached to the aromatic ring of the styrene moiety via a para bond.

[0052]

[0053] In the above embodiment, a-2t) is an ABA triblock copolymer comprising a middle B) block segment having repeating units of acrylic structure (Ia) and two end block B) segments of equal length having styrene structure (IIa), wherein R 1a and R 3a are independently selected from H and C-1 to C-4 alkyl, R 2a is H or C-1 to C-8 alkyl, R 4ais a C-1 to C-8 alkyl group, based on the total moles of repeating units of structures (Ia) and (IIa), the mole % value of repeating units of structure (Ia) is from about 40 mole % to about 80 mole %, and the mole % value of repeating units of structure (IIa) is from about 20 mole % to about 60 mole %, wherein the individual values ​​of the mole % of repeating units of structures (Ia) and (IIa) are selected from their respective ranges so that the total moles of repeating units of structures (Ia) and (IIa) add up to 100 mole %, and the polydispersity of the triblock copolymer a-2t) is from about 1.0 to about 1.1, and M n In one aspect of this embodiment, part R 2a The aromatic ring is attached to the styrene moiety via a para bond.

[0054]

[0055] In another aspect of the composition of the present invention, component a) is an ABA triblock copolymer selected from repeating units of structures (I), (II), (Ia) and (IIa), a-1t), a-2t), or a blend thereof. In another aspect of this embodiment, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a is independently selected from C-1 to C-4 alkyl. In another aspect of this embodiment. In another aspect of this embodiment, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a In another aspect of this embodiment, R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a It's methyl.

[0056] In another aspect of the composition of the present invention, wherein component a) is an ABA triblock copolymer, it is a triblock copolymer selected from the group consisting of a triblock copolymer of structure (ABA-1), a triblock copolymer of structure (ABA-2), and a mixture of these two block copolymers. In this embodiment, mt, mta, nt, and nta are the number of repeating units, R 1s , R 1sa , R 2s and R 2sa independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s and Si(R 5s )3, where R3s , R 4s and R 5s In a more specific aspect of this embodiment, R1, R 1a , R2, R 2a and R 1s and R 2s is H and R3, R 3a , R4 and R 4a In another more specific aspect of this embodiment, R1, R 1a , R2, R 2a and R 1s and R 2s is H and R3, R 3a , R4 and R 4a It's methyl.

[0057]

[0058] Component a) is a diblock polymer

[0059] In another aspect of the inventive compositions described herein, component a) is a diblock copolymer or a blend of at least two diblock copolymers. In one aspect of this embodiment, it is selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2), and blends of a-1) and a-2), wherein a-1) and a-2) are as follows:

[0060] a-1) is a diblock copolymer of a block A) having a repeating unit of structure (I) and a block B) having a repeating unit of structure (II), wherein R1 and R3 are independently selected from H and C-1 to C-4 alkyl, R2 is H or C-1 to C-8 alkyl, and R4 is C-1 to C-8 alkyl. In addition, based on the total moles of the repeating units of structures (I) and (II), the mole % value of the repeating units of structure (I) is from about 40 mole % to about 80 mole % and the mole % value of the repeating units of structure (II) is from about 20 mole % to about 60 mole %. In addition, the respective values ​​of the mole % of the repeating units of structures (I) and (II) are selected from their respective ranges so that the total moles of the repeating units of structures (I) and (II) add up to 100 mole %, and the polydispersity of the diblock copolymer a-1) is from about 1.0 to about 1.1 and M n From about 50,000 g / mol to about 150,000 g / mol. In one aspect of this embodiment, the moiety R2 is attached to the aromatic ring of the styrene moiety via a para-linkage.

[0061]

[0062] a-2) is a diblock copolymer of a block Aa) having a repeating unit of structure (Ia) and a block Ba) having a repeating unit of structure (IIa). 1a and R 3a are independently selected from H or C-1 to C-4 alkyl, R 2a is H or C-1 to C-8 alkyl, R 4a is a C-1 to C-8 alkyl group. Based on the total moles of the repeating units of structures (Ia) and (IIa), the mole % value of the repeating units of structure (Ia) is about 40 mol % to about 80 mol % and the mole % value of the repeating units of structure (IIa) is about 20 mol % to about 60 mol %. In addition, the respective values ​​of the mole % of the repeating units of structures (Ia) and (IIa) are selected from their respective ranges so that the total moles of the repeating units of structures (Ia) and (IIa) add up to 100 mol %. In addition, the polydispersity of the diblock copolymer a-2) is about 1.0 to about 1.1 and M n In one aspect of this embodiment, part R 2a The aromatic ring is connected to the styrene portion through a para-linkage. In more specific aspects of these diblock copolymer embodiments, R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a In more specific aspects of these embodiments, R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a It's methyl.

[0063]

[0064] In another aspect of the above-mentioned composition of the present invention, the diblock copolymer components a-1) and a-2) are wherein R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a In more specific aspects of this embodiment, R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a Each is a methyl group.

[0065] In any of the compositions of the present invention, wherein component a) is the diblock copolymer components a-1) and a-2), wherein there is a spacer moiety between the two blocks, the spacer moiety being a moiety derived from a 1,1-diphenylethylene derivative. In this embodiment, a-1) and a-2) have structures (IS) and (ISa), respectively, wherein R 1s , R 1sa , R 2s and R 2sa independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s and Si(R 5s )3, where R 3s , R 4s and R 5s In another aspect of this embodiment, R 1s , R 2s , R 1sa and R 2sa is hydrogen. In the structures (IS) and (ISa), the polymer blocks block A) and block Aa) (also known as styrene blocks) are connected by secondary (i.e. when R1 or R 1a = hydrogen) or tertiary (that is, when R2 or R 2a =C-1 to C-4 alkyl) are terminally connected to these spacer moieties. Correspondingly, polymer segments block B) and block Ba) are terminally connected to the spacer moieties (IS) and (ISa) of the acrylic repeating units at the ends of these blocks via the primary positions (i.e., CH2 moieties) on the "acrylic" repeating units.

[0066]

[0067] In any of the above aspects of the composition of the present invention, wherein component a) comprises a diblock copolymer component a-1), the polydispersity of the component is from about 1.00 to about 1.03. In another aspect of this embodiment, the M of component a-1) is n From about 93,000 g / mol to about 105,300 g / mol.

[0068] In other aspects of the composition of the present invention, in component a), the diblock copolymer component a-1), the mole % of repeating units of structure (I) is about 60 mole % to about 80 mole %, and the mole % of repeating units of structure (II) is about 20 mole % to about 40 mole %.

[0069] In another aspect of this embodiment, wherein component a) is a diblock copolymer comprising about 60 mol% to about 75 mol% of repeating units of structure (I) and about 25 mol% to about 40 mol% of repeating units of structure (II). In one aspect of the composition of the present invention, in component a), the diblock copolymer component a-1), the mole % of structure (I) is about 40 mol% to about 60 mol%, and the repeating units of structure (II) are about 40 mol% to about 60 mol%.

[0070] In any of the above aspects of the composition of the present invention, wherein for component a), the polydispersity of the diblock copolymer component a-2) is from about 1.00 to about 1.03.

[0071] In any of the above aspects of the composition of the present invention, wherein the component a) diblock copolymer comprises component a-2), the M of the component n From about 40,800 g / mol to about 61,200 g / mol.

[0072] In any of the above aspects of the composition of the present invention, for component a), in a single block copolymer a-1) or a-2) or a blend of a-1) and a-2), the total mole % value of repeating units of structures (I) and (Ia) is from about 40 mole % to about 60 mole % and the total mole % value of repeating units of structures (II) and (IIa) is from about 40 mole % to about 60 mole %.

[0073] In any of the above aspects of the composition of the present invention, for component a), in a single block copolymer a-1) or a-2) or a blend of a-1) and a-2), the total mole % value of repeating units of structures (I) and (Ia) is from about 60 mole % to about 75 mole % and the total mole % value of repeating units of structures (II) and (IIa) is from about 25 mole % to about 40 mole %.

[0074] In one aspect of the above-mentioned composition of the present invention, component a) may be a blend of a-1) and a-2).

[0075] In one aspect of the above-mentioned composition of the present invention, component a) is a-1) or a-2).

[0076] In one aspect of the above-mentioned composition of the present invention, when component a) is diblock copolymer a-1), diblock copolymer a-2) or a blend of a-1) and a-2), the total mole % value of the repeating units of structures (I) and (Ia) present in component a) (based on the total moles of all repeating units) is from about 45 mole % to about 75 mole %, and correspondingly, the sum of the mole % of the repeating units of structures (II) and (IIa) is from about 25 mole % to about 55 mole %.

[0077] In any of the above aspects of the composition of the present invention, when component a) comprises a diblock copolymer or a triblock copolymer, the wt % of component a) is from about 0.5 wt % to about 2.00 wt % of the total weight of the total composition.

[0078] Component b)

[0079] In any of the above aspects of the compositions of the present invention comprising oligomeric diblock copolymer components b-2) and b-3), respectively, they may have a spacer between block Ab) and block Bb) or between block Ac) and block Bc), respectively, as shown in Structure (ISb) and Structure (ISc), respectively, wherein R 1sb , R 1sc , R 2sb and R 2sc independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s 、Si(R 5s )3, where R 3s , R 4s and R 5s In another aspect of this embodiment, R 1sb , R 2sb , R 1sc and R 2sc It's hydrogen.

[0080] In the structures (ISb) and (ISc), the polymer blocks block Ab) and block Ac) (also called styrene blocks), these block chains are terminally connected to these spacer moieties via secondary (i.e. when R5 or R7 = hydrogen) or tertiary (i.e. when R5 or R7 = C-1 to C-4 alkyl) positions. Correspondingly, the polymer blocks block Bb) and block Bc) are terminally connected to the acrylic repeating unit spacer moieties (ISb) and (ISc), respectively, via primary positions (i.e. CH2 moieties) on the "acrylic" repeating units at the ends of these blocks.

[0081]

[0082] In any of the above aspects of the composition of the present invention comprising the oligomeric random copolymer b-1), wherein R 1b and R 2b is H and R 3b and R 4b It is a composition of methyl.

[0083] In any of the above aspects of the composition of the present invention comprising the oligomeric random copolymer b-1), the oligomeric random copolymer b-1) has a polydispersity of from about 1.3 to about 1.5.

[0084] In any of the above aspects of the composition of the present invention, wherein for component b), the M of the oligomeric random copolymer b-1) is n From about 1000 g / mol to about 5000 g / mol.

[0085] In any of the above aspects of the composition of the present invention, wherein for component b), the oligomeric random copolymer b-1) has a polydispersity of from about 1.3 to about 1.6.

[0086] In any of the above aspects of the composition of the present invention, wherein component b) comprises an oligomeric random copolymer b-1), and the T of the component g From about 50°C to about 90°C.

[0087] In one aspect of the above-mentioned composition of the invention, component b) is an oligomeric random copolymer b-1).

[0088] In the above aspect of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-2) wherein R5, R7 and R8 are H, R6 is n-octyl or n-nonyl, R9 and R 11 is methyl, R 10 is methyl or ethyl, R 12 and R 13 are independently ethylene or propylene, R 14 In another aspect of this embodiment, the oligomeric diblock copolymer b-2) is wherein R6 is n-octyl, R 10 is methyl, R 12 and R 13 is ethylene, and R 14 It is a methyl oligomeric diblock copolymer.

[0089] In one aspect of any of the above-described compositions of the present invention, component b) comprises an oligomeric diblock copolymer b-2), wherein the mole % of the sum of the mole % of repeating units (III) and (IV) is from about 40 mole % to about 80 mole %, and the sum of the mole % of repeating units (V) and (VI) is in the range of about 20 mole % to about 60 mole %, based on the total moles of repeating units having structures (III), (IV), (V) and (VI), and further, wherein the mole % of repeating units (III) is in the range of about 2 mole % to about 80 mole %, and the mole % of repeating units (VI) is in the range of about 1 mole % to about 80 mole %. In another aspect of this embodiment, the mole % of repeating units (III) is from about 2 mole % to about 64 mole %. In another aspect of this embodiment, the mole % of (VI) is in the range of about 2 mole % to about 48 mole %.

[0090] In all embodiments described herein for the oligomeric diblock copolymer b-2), the individual values ​​for the mole % of repeating units of structures (III), (IV), (V) and (VI) are selected from their respective ranges such that the total moles of repeating units of structures (III), (IV), (V) and (VI) add up to 100 mole %.

[0091] In other aspects of the composition of the present invention, in the oligomeric diblock copolymer b-2), the mole % of repeating units of structure (IV) is about 25 mole % to about 50 mole %, and the mole % of repeating units of structure (V) is about 40 mole % to about 60 mole %.

[0092] In another aspect of the composition of the present invention, in the oligomeric diblock copolymer b-2), the mole % of repeating units of structure (III) is about 20% to about 30% of the mole % of repeating units of structure (IV), and the mole % of repeating units of structure (VI) is about 12% to about 20% of the mole % of repeating units of structure (V).

[0093] In another aspect of the above-mentioned composition of the present invention, when component a) is a diblock copolymer a-1), a diblock copolymer a-2), or a blend of a-1) and a-2), as described above, for the oligomeric diblock copolymer b-2), the mole % composition of block Ab) and block Bb) as a whole varies according to the phase morphology window of the diblock copolymer component a). Specifically, for example, when the mole % of the sum of repeating units of structures (III) and (IV) in block Ab) is selected from about 40 mole % to about 80 mole %, when component a) is a diblock copolymer a-1), a diblock copolymer a-2), or a blend of a-1) and a-2), the specific sum value selected within this range will match the total mole % value of repeating units of structures (I) and (Ia) present in component a). Accordingly, in block Bb), when the sum of the mole % of repeating units of structures (V) and (VI) is from about 25 mole % to about 55 mole %, when component a) is diblock copolymer a-1), diblock copolymer a-2) or a blend of a-1) and a-2), the specific sum value selected within this range will match the total mole % value of repeating units of structures (II) and (IIa) present in component a).

[0094] In the above aspect of the composition of the present invention, wherein component b) comprises an oligomeric diblock copolymer b-2) having a polydispersity of from about 1.03 to about 1.08.

[0095] In the above aspect of the composition of the present invention, wherein for component b), an oligomeric diblock copolymer b-2) is included, wherein M nFrom about 15000 g / mol to about 32000 g / mol, for example, from about 15000 g / mol to about 30000 g / mol.

[0096] In the above aspect of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-2) having a T g From about 50°C to about 90°C.

[0097] In one aspect of the above-mentioned composition of the invention, component b) is an oligomeric diblock copolymer b-2).

[0098] Any composition of the present invention, wherein in component b) and the oligomeric diblock copolymer b-3), R 1c and R 2c is H and R 3c and R 4c In another aspect of this embodiment, R 1c and R 2c is H and R 3c and R 4c It's methyl.

[0099] In the above aspect of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-3) and its M n From about 15,000 to about 30,000 g / mol.

[0100] In the above aspect of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-3) and has a polydispersity of about 1.02 to about 1.08.

[0101] In the above aspects of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-3), wherein the mole % of repeating units of structure (Ic) is from about 40 mole % to about 70 mole %, and the mole % of repeating units of structure (IIc) is from about 40 mole % to about 70 mole %.

[0102] In the above aspect of the composition of the present invention, component b) comprises an oligomeric diblock copolymer b-3) having a g From about 50°C to about 90°C.

[0103] In one embodiment of the above-described composition of the invention, component b) is a diblock copolymer b-3).

[0104] In one embodiment of the above-described composition of the present invention suitable for L / S applications, a) the diblock copolymer component a-1), the mole % value of the repeating units of structure (I) is from about 40 mole % to about 60 mole % and the mole % value of the repeating units of structure (II) is from about 40 mole % to about 60 mole %.

[0105] In one embodiment of the above-described composition of the present invention suitable for CH applications, a), in the diblock copolymer component a-1), the mole % value of the repeating units of structure (I) is from about 60 mole % to about 75 mole %, and the mole % value of the repeating units of structure (II) is from about 25 mole % to about 40 mole %.

[0106] In any of the above-mentioned component b) embodiments, the component can be about 0.05wt% to about 0.5wt% of the total weight of the composition including the spin-cast organic solvent. In another aspect of this embodiment, it is about 0.08wt% to about 0.4wt%. In another aspect of this embodiment, it is about 1wt% to about 0.4wt%. In another aspect of this embodiment, it is about 0.15wt% to about 0.4wt%. In another aspect of this embodiment, it is about 0.2wt% to about 0.3wt%. In another aspect of this embodiment, component b) is b-1). In another aspect of this embodiment, component b) is b-2). In another embodiment, component b) is b-3). In another aspect of this embodiment, component b) is a mixture of at least two components b) selected from the group consisting of b-1), b-2) and b-3).

[0107] Component c)

[0108] For component c), spin-casting organic solvents, suitable solvents for dissolving the above-mentioned composition of the present invention include glycol ether derivatives, such as ethyl cellosolve, methyl cellosolve, propylene glycol monomethyl ether (PGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol dimethyl ether, propylene glycol n-propyl ether or diethylene glycol dimethyl ether; glycol ether ester derivatives, such as ethyl cellosolve acetate, methyl cellosolve acetate or propylene glycol monomethyl ether acetate (PGMEA); carboxylic acid esters, such as ethyl acetate, n-butyl acetate and amyl acetate; carboxylic acid esters of dibasic acids, such as diethyloxylate and diethyl ethyl propionate; methyl malonate; dicarboxylic acid esters of glycols, such as ethylene glycol diacetate, propylene glycol diacetate; and hydroxycarboxylic acid esters such as methyl lactate, ethyl lactate (EL), ethyl glycolate and ethyl 3-hydroxypropionate; ketoesters, such as methyl pyruvate or ethyl pyruvate; alkoxycarboxylates, such as methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 2-hydroxy-2-methylpropionate or methyl ethoxypropionate; ketone derivatives, such as methyl ethyl ketone, acetylacetone, cyclopentanone, cyclohexanone or 2-heptanone; ketoether derivatives, such as diacetone alcohol methyl ether; ketoalcohol derivatives, such as acetone alcohol or diacetone alcohol; ketals or acetals, such as 1,3-dimethoxypropionate; alkanes and diethoxypropane; lactones, such as butyrolactone; amide derivatives, such as dimethylacetamide or dimethylformamide, anisole and mixtures thereof.

[0109] In addition, the above-mentioned composition of the present invention may also include additives selected from the group consisting of: surfactants, inorganic-containing polymers; additives containing small molecules, inorganic-containing molecules, surfactants, photoacid generators, thermal acid generators, quenchers, hardeners, cross-linkers, chain extenders, etc.; and a combination comprising at least one of the foregoing substances, wherein one or more additional components and / or additives are co-assembled with the block copolymer to form a block copolymer assembly.

[0110] Method of the present invention

[0111] The inventive compositions described herein can be used in unguided self-assembly processes to produce arrays of features or in directed (aka guided) self-assembly processes such as graphoepitaxy or chemoepitaxy to effect pattern correction or pattern multiplication of guided features of chemoepitaxy or graphoepitaxy.

[0112] After self-assembly, these patterns can be transferred to the substrate below by using plasma. Typically, anisotropic etching of oxygen-containing plasma for etching resists (e.g., JBKruger et al., "VLSI Electronics, Microstructure Science," Chapter 5, Academic Press, pp. 91-136, 1984) is most commonly used to etch semiconductor substrates using self-assembled films of methyl methacrylate and polystyrene block copolymers as masks (e.g., 'Etch considerations for directed self-assembly patterning using capacitively coupled plasma, "Vinayak Rastogi et al, Journal of Vacuum Science & Technology A36, 031301, 2018). Since the novel compositions described herein include such block copolymers, these general types of conditions can be used to affect the pattern transfer of the self-assembled films of the compositions of the present invention to substrates.

[0113] One aspect of the invention is a method comprising the steps of:

[0114] i) forming a coating of a neutral layer on a substrate,

[0115] ii) applying any of the above compositions of the present invention onto the neutral layer to form a film,

[0116] ii) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0117] iii) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

[0118] Another aspect of the invention is a method of forming a line and space array comprising the steps of:

[0119] ia) forming a coating of a neutral layer on a substrate,

[0120] iia) applying the above-mentioned composition of the invention suitable for L / S application onto the neutral layer to form a film,

[0121] iiia) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0122] iva) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate to form an L / S array.

[0123] Another aspect of the present invention is a method for forming a line and space L / S pattern by a graphene epitaxy process, comprising the following steps:

[0124] ia') forming a coating of a neutral layer on a substrate,

[0125] iia') coating a photoresist on the top of the coating layer of the neutral layer to form a photoresist film,

[0126] iiia') patterning the photoresist to produce an L / S patterned photoresist,

[0127] iva′) applying the above composition of the present invention suitable for L / S application onto the patterned photoresist to produce a film of the composition of the present invention suitable for L / S in which the L / S pattern is filled with and flush with the surface of the photoresist,

[0128] va') baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0129] The substrate is then etched with plasma to transfer the self-assembled film pattern into the substrate to form an L / S pattern.

[0130] Another aspect of the present invention is a method of forming a line and space (L / S) pattern by a chemical epitaxial process, comprising the steps of:

[0131] ia") forming a coating of a neutral layer on a substrate,

[0132] iia”) coating a photoresist on the top of the coating of the neutral layer to form a photoresist film,

[0133] iiia”) patterning the photoresist to produce an L / S patterned photoresist film,

[0134] iva”) using the patterned photoresist film as a mask to etch the underlying neutral layer,

[0135] va”) to strip the resist to form a patterned neutral layer, which is a chemical epitaxial pattern without significant morphology,

[0136] via ") coating the above-mentioned composition of the present invention suitable for L / S application on the patterned neutral layer to form a block copolymer film,

[0137] viia") baking the block copolymer film at a temperature selected from about 240°C to about 260°C in an inert gas atmosphere to form a self-assembled film, and

[0138] viiia") etching the substrate with plasma to transfer the self-assembled film pattern into the substrate to form an L / S pattern.

[0139] Another aspect of the present invention is a method for forming a contact hole (CH) array, comprising the following steps:

[0140] ib) forming a coating of a neutral layer on a substrate,

[0141] iib) applying the above composition suitable for CH application onto the neutral layer to form a film,

[0142] iiib) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0143] ivb) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate to form a CH array.

[0144] Another aspect of the present invention is a method for forming a contact hole (CH) pattern by a graphene epitaxy process, comprising the following steps:

[0145] ib') forming a coating of a neutral layer on a substrate,

[0146] iib′) coating a photoresist on the top of the coating layer of the neutral layer to form a photoresist film,

[0147] iiib') patterning the photoresist to produce a CH patterned photoresist,

[0148] ivb′) applying the above-mentioned composition of the present invention suitable for CH application onto the patterned photoresist to produce a film of the composition of the present invention suitable for L / S in which the L / S pattern is filled with and flush with the photoresist surface,

[0149] vib') baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0150] viib′) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate to form a CH pattern.

[0151] Another aspect of the present invention is a method of forming lines and spaces by a chemical epitaxial process, comprising the steps of:

[0152] ib")) forming a coating of a neutral layer on a substrate,

[0153] iib”) coating a photoresist on the top of the coating layer of the neutral layer to form a photoresist film,

[0154] iiib”) patterning the photoresist to produce a CH patterned photoresist,

[0155] ivb”) using the patterned photoresist as a mask to etch the underlying neutral layer,

[0156] vb”) to strip the resist, forming a patterned neutral layer, which is a chemical epitaxial pattern without significant morphology,

[0157] vib″) coating the above-mentioned composition of the present invention suitable for CH application on the patterned neutral layer to form a block copolymer film,

[0158] viib") baking the block copolymer film at a temperature selected from about 240°C to about 260°C in an inert gas atmosphere to form a self-assembled film, and

[0159] viiib′) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate to form a CH pattern.

[0160] In the above-mentioned method of the present invention, when the composition of the present invention is applied to a substrate to form a coating, it can be heated in an additional step to remove the spin casting organic solvent in a different separate step before the heating step of producing the self-assembled film. For this additional step, the film can be heated at a temperature range of about 100°C to about 150°C or about 120°C to about 150°C.

[0161] Typical film thicknesses after heating are in the range of about 25 nm to about 70 nm, or about 40 nm to about 60 nm, or about 45 nm to about 55 nm, or about 45 nm to about 52 nm.

[0162] It is also expected that the novel compositions described above for CH or L / S can be used in other chemical epitaxy and graphoepitaxy processes or hybrid processes combining the two. For example, in chemical epitaxy, the guided pinning features can be patterned discrete organic pinning layers, rather than just uncovered bare semiconductor substrate areas. For example, the patterned pinning layer can be above the neutral layer, or below the patterned pinning layer.

[0163] The composition of the present invention that can be used to form a contact hole array is a composition comprising component a), wherein component a) is a diblock copolymer component selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2), and blends of a-1) and a-2), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is from about 60 mole % to about 75 mole %, and the total mole % of acrylic repeating units of structures (II) and (IIa) is from about 40 mole % to about 60 mole %, and wherein component b) can be selected from copolymers b-1), copolymers b-2), such as oligomeric diblock copolymers b-2) or copolymers b-3) and mixtures of these. In one aspect of this embodiment, component b) is only oligomeric random copolymers b-1), in another aspect, component b) is only copolymers b-2), and in yet another aspect, component b) is only copolymers b-3).

[0164] The composition of the present invention useful for forming line and space (L / S) arrays is a composition wherein component a) is a diblock copolymer component selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2), and blends of a-1) and a-2), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is from about 60 mole % to about 75 mole %, and further wherein the total mole % of acrylic repeating units of structures (II) and (IIa) is from about 25 mole % to about 40 mole %, and component b) is a copolymer b-1), such as an oligomeric random copolymer b-1), a copolymer b-2), such as an oligomeric diblock copolymer b-2), or a copolymer b-3), such as an oligomeric diblock copolymer b-3). In one aspect of this embodiment, component b) is solely the oligomeric random copolymer b-1), in another aspect, component b) is solely the copolymer b-2), and in yet another aspect, component b) is solely the copolymer b-3).

[0165] The composition of the present invention useful for forming line and space (L / S) arrays is a composition wherein component a) is selected from the group consisting of triblock copolymer component a-1t), triblock copolymer a-2t), and blends of a-1t) and a-2t), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is from about 60 mole % to about 75 mole % and the total mole % of acrylic repeating units of structures (II) and (IIa) is from about 40 mole % to about 60 mole %, and component b) is copolymer b-2 or copolymer b-3), such as an oligomeric diblock copolymer b-3). In one aspect of this embodiment, component b) is only copolymer b-2), and in another aspect, component b) is only copolymer b-3).

[0166] The composition of the present invention that can be used to form a contact hole array is such a composition, wherein component a) is selected from the group consisting of triblock copolymer component a-1t), triblock copolymer a-2t) and a blend of a-1t) and a-2t), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is from about 60 mole % to about 75 mole %, and further, wherein the total mole % of acrylic repeating units of structures (II) and (IIa) is from about 25 mole % to about 40 mole %, and component b) is copolymer b-2), such as oligomeric diblock copolymer b-2), or copolymer b-3), such as oligomeric diblock copolymer b-3). In one aspect of this embodiment, component b) is only copolymer b-2), and in another aspect, component b) is only copolymer b-3).

[0167] Another aspect of the present invention is a method for forming a contact hole array, comprising the steps of:

[0168] i) forming a coating of a neutral layer on a substrate,

[0169] ii) applying a composition comprising the above diblock copolymer suitable for forming a contact hole array onto the neutral layer to form a film,

[0170] ii) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0171] iii) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

[0172] In one aspect of this embodiment, component b) is an oligomeric random copolymer b-1), in another aspect, component b) is a copolymer b-2), and in yet another aspect, component b) is a copolymer b-3).

[0173] Another aspect of the present invention is a method of forming an L / S array, comprising the steps of:

[0174] ib) forming a coating of a neutral layer on a substrate,

[0175] iiib) applying a composition comprising the above-mentioned diblock copolymer suitable for forming an L / S array onto the neutral layer to form a membrane,

[0176] ivb) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0177] vb) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

[0178] In one aspect of this embodiment, component b) is an oligomeric random copolymer b-1), in another aspect, component b) is a copolymer b-2), and in yet another aspect, component b) is a copolymer b-3).

[0179] A method of forming a line and space array comprising the steps of:

[0180] ic) forming a coating of a neutral layer on a substrate,

[0181] iiic) applying a composition comprising the above triblock copolymer suitable for forming an L / S array onto the neutral layer to form a membrane,

[0182] ivc) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0183] vc) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

[0184] The method for forming a contact hole array comprises the following steps:

[0185] id) forming a coating of a neutral layer on a substrate,

[0186] iiid) applying a composition comprising the above triblock copolymer suitable for forming a contact hole array onto the neutral layer to form a film,

[0187] ivd) baking the film at a temperature selected from about 240° C. to about 260° C. in an inert gas atmosphere to form a self-assembled film, and

[0188] vd) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

[0189] Oligomeric diblock copolymers of the present invention

[0190] Another aspect of the present invention is an oligomeric diblock copolymer according to the present invention, comprising a block Ab) and a block Bb), M n The molecular weight of the present invention is about 1,000 to 35,000 g / mol and the polydispersity is 1.0 to about 1.1. In the material of the present invention, block Ab) is a random copolymer having repeating units of structures (III) and (IV), and block Bb) is a random copolymer having repeating units of structures (V) and (VI). Further, in the novel oligomeric diblock copolymer, R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, R6 is C-7 to C-10 straight chain alkyl, R8 is C-1 to C-4 alkyl, R 10 is a C-1 to C-4 alkyl group, R 12 and R 13 are each selected from C-2 to C-5 alkylene, and R 14 is C-1 to C-4 alkyl, R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, R6 is C-7 to C-10 straight chain alkyl, R8 is C-1 to C-4 alkyl, R 10 is a C-1 to C-4 alkyl group, R 12 and R 13 are each selected from C-2 to C-5 alkylene, and R 14 is a C-1 to C-4 alkyl group, and further, the T g A value of about 0°C to about 95°C.

[0191]

[0192] In one aspect of the oligomeric diblock copolymer of the present invention, the mole % values, based on the total moles of repeating units of structures (III), (IV), (V) and (VI), are as follows:

[0193] For the repeating unit of structure (IV), the mole % is from about 10 mole % to about 50 mole %,

[0194] For the repeating unit of structure (V), the mol % is from about 20 mol % to about 60 mol %,

[0195] For repeating units of structure (III), the mole % thereof is from about 10% to about 0% of the mole % of repeating units of structure (IV),

[0196] For the repeating units of structure (VI), the mole % thereof is from about 10% to about 40% of the mole % of the repeating units of structure (V), and the individual values ​​of the mole % of the repeating units of structures (III), (IV), (V) and (VI) are selected from their respective ranges so that the total moles of the repeating units of structures (III), (IV), (V) and (VI) add up to 100 mole %.

[0197] In another aspect of the above oligomeric diblock copolymer of the present invention, it has a spacer between block Ab) and block Bb), as shown in structure (ISb), wherein R 1sb and R 2sb independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s 、Si(R 5s )3, where R 3s , R 4s and R 5s In another aspect of this embodiment, R 1sb and R 2sb It's hydrogen.

[0198]

[0199] In another aspect of the above oligomeric diblock copolymer of the present invention, R5, R7 and R8 are H, R6 is a C-8 to C-9 straight chain alkyl, R9 and R 11 is methyl, R 10 is methyl or ethyl, R 12 and R 13 are independently ethylene or propylene, and R 14 In another aspect of this embodiment, R6 is n-octyl, R 10 is methyl, R 12 and R 13 is ethylene, and R 14 It's methyl.

[0200] In another aspect of the above oligomeric diblock copolymer of the present invention, its M n From about 15,000 to about 25,000 g / mol.

[0201] In another aspect of the above oligomeric diblock copolymer of the present invention, the mole % of repeating units of structure (IV) is from about 25 mole % to about 50 mole % and the mole % of repeating units of structure (V) is from about 40 mole % to about 60 mole %.

[0202] In another aspect of the above oligomeric diblock copolymer of the present invention, the mole % of the sum of the mole % of repeating units (III) and (IV) is from about 40 mole % to about 80 mole %, and the mole % of repeating units (V) and (VI) is in the range of about 20 mole % to about 60 mole %, based on the total moles of repeating units having structures (III), (IV), (V) and (VI), and further, the mole % of repeating units (III) is in the range of about 2 mole % to about 80 mole %, and the mole % of repeating units (VI) is in the range of about 1 mole % to about 80 mole %, and further, the individual values ​​of the mole % of repeating units of structures (III), (IV), (V) and (VI) are selected from their respective ranges so that the total moles of repeating units of structures (III), (IV), (V) and (VI) add up to 100 mole %.

[0203] In another aspect of the above oligomeric diblock copolymer of the present invention, the mole % of repeating unit (III) is from about 2 mole % to about 64 mole %.

[0204] In another aspect of the above oligomeric diblock copolymer of the present invention, the mole % of (VI) is from about 2 mole % to about 48 mole %.

[0205] In another aspect of the above-mentioned oligomeric diblock copolymer of the present invention, the mole % of repeating units of structure (III) is about 20% to about 30% of the mole % of repeating units of structure (IV), and for repeating units of structure (VI), its mole % is about 12% to about 20% of the mole % of repeating units of structure (V).

[0206] In all embodiments described herein for the novel oligomeric diblock copolymers, the individual values ​​of the mole % of repeating units of structures (III), (IV), (V) and (VI) are selected from their respective ranges described herein so that the total moles of repeating units of structures (III), (IV), (V) and (VI) add up to 100 mole %.

[0207] In another aspect of the above oligomeric diblock copolymer of the present invention, the oligomeric diblock copolymer has a polydispersity of from about 1.03 to about 1.08.

[0208] In another aspect of the above oligomeric diblock copolymer of the present invention, wherein the M of the oligomeric diblock copolymer is n From about 15,000 g / mol to about 32,000 g / mol.

[0209] In another aspect of the above oligomeric diblock copolymer of the present invention, the T g From about 50°C to about 90°C.

[0210] A further aspect of the invention is the use of the composition according to the invention or of the oligomeric diblock copolymer according to the invention for producing a self-assembled film on a substrate. Example

[0211] Chemicals

[0212] Unless otherwise stated, all chemicals were purchased from Sigma Aldrich (3050 Spruce St., St. Louis, MO 63103). Chemicals used in anionic polymerization were purified as described in the literature (e.g., Techniques in High-Vacuum Anionic Polymerization" By David Uhrig and Jimmy Mays and Journal of Polymer Science: Part A: Polymer Chemistry, Vol. 43, 6179-6222 (2005)).

[0213] All synthesis experiments were performed under N2 atmosphere. Photolithography experiments were performed as described in the text. The molecular weight of the copolymers was measured by gel permeation chromatography. The gel permeation chromatograph was equipped with and μ-ultrastyragel column.

[0214] The photolithography experiments were performed using a TEL Clean ACT8 track. The SEM images were taken using an Applied Materials NanoSEM_3D scanning electron microscope, and the images were displayed at 1FOV magnification or 2FOV magnification (field of view (FOV) = 5 μm).

[0215] Etching experiments were performed on self-assembled monolayer block copolymers of methyl methacrylate and styrene using standard isotropic oxygen etching conditions.

[0216] Unless otherwise stated, molecular weight measurements (also known as M n Polydispersity) is determined by and Gel permeation chromatography was performed on a μ-ultrastyragel column (PSS Inc. Germaby) using THF solvent as eluent. Polystyrene polymer standards were used for calibration.

[0217] DSC measurements of glass transition temperature were performed using a TA Instruments DSC Q1000 under nitrogen at a heating rate of 10°C / min. The glass transition temperature (T g). Consider the midpoint of the endothermic transition.

[0218] 1 H NMR spectra were recorded using a Bruker Advanced III 400 MHz spectrometer.

[0219] Synthesis Example 1: Synthesis of PS-co-PMMA Neutral Layer Material

[0220] A 250-ml flask equipped with a temperature controller, a heating jacket and a magnetic stirrer was set up. 26.04g (0.25mol) of styrene, 24.03g (0.24mol) of methyl methacrylate, 1.42g (0.10mol) of glycidyl methacrylate, 0.41g (0.0025mol) of azobisisobutyronitrile (AIBN) initiator and 100g of anisole were added to the flask. The agitator was turned on and set at about 400rpm. The reaction solution was then degassed by bubbling nitrogen through the solution vigorously for about 30 minutes at room temperature. After degassing for 30 minutes, the heating jacket was turned on and the temperature controller was set at 70°C, and the stirred reaction mixture was kept at this temperature for 20 hours. Thereafter, the heating jacket was turned off and the reaction solution was cooled to about 40°C. The reaction mixture was then poured into 1.5L of isopropanol and mechanically stirred during the addition process. During this addition process, the polymer precipitated out. The precipitated polymer was collected by filtration. The collected polymer was dried in a vacuum oven at 40°C. About 36 g of polymer was obtained. The dried polymer was dissolved in 300 g of THF and then filtered through a 0.2 μm nylon filter. The filtered solution was then precipitated again into 1.5 L of a stirred methanol solution, and the precipitated polymer was collected and dried under vacuum at 40° C. as before. In this way, 26 g (50% yield) of polymer was obtained after drying. The M of the polymer was w The polydispersity (PDI) is about 36k and 1.5.

[0221] Synthesis Example 2: Synthesis of P(Sb-MMA)(78K-b-39K)

[0222] Styrene and methyl methacrylate monomers were distilled into calibrated ampoules in the presence of a dehydrating agent and stored under N2. The liquid was transferred to the reactor via an ampoule or using a stainless steel cannula under N2. 700 mL of dry tetrahydrofuran was added to a dry 1L round-bottom reactor equipped with a side arm for connecting the ampoule, a magnetic stirring bar, and a nitrogen / vacuum three-way septum adapter. The temperature of the reactor was lowered to -78°C using a dry ice-acetone bath. Then, after titration of impurities, 0.2 mL (1.4 M solution) of sec-butyl lithium was added to the reactor. Then, 20 g (0.192 mol) of styrene was added to the reactor from an ampoule under rapid stirring. The reaction solution turned orange-yellow, and the reaction was stirred for 30 minutes. Subsequently, 0.06 g (0.0003 mol) of 1,1'-diphenylethylene (DPE) in 2.5 ml of dry toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned into a dark brick red, indicating that the styrene lithium active center was converted into a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Methyl methacrylate (9.98 g, 0.0998 mol) was then added via an ampoule. The reaction was terminated with 1 mL of degassed methanol after 30 minutes. The block copolymer was recovered by precipitation in excess isopropanol (5 times the polymer solution) containing 10% water, filtration, and vacuum drying at 55°C for 12 hours to obtain 28 g of P(Sb-MMA) (94% yield) consisting of 66 mol% polystyrene blocks and 34 mol% polymethyl methacrylate blocks.

[0223] Equipped with and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first P(SDPE) block was n (GPC) = 64,622 g / mol and M w / M n =1.02. The molecular weight of the diblock copolymer obtained from GPC is M n,PS-b-PMMA =107,150 g / mol and M w / M n =1.01.

[0224] Synthesis Example 3: Synthesis of P(Sb-MMA)(34K-17K)

[0225] PS-PMMA (34-17K) was synthesized using the same procedure as described in Example 2. In order to achieve the target M of PS block and PMMA block. n , while keeping the amounts of styrene and MMA the same as in Example 2, 0.42 mL of 1.4 M sec-butyllithium solution was added.

[0226] Equipped with and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first P(SDPE) block was n (GPC) = 34,872 g / mol and M w / M n =1.03. The molecular weight of the diblock copolymer obtained from GPC is M n,PS-b-PMMA =49,240 g / mol and M w / M n =1.02. 1 H NMR showed 66.1 mol % of polystyrene blocks and 33.9 mol % of polymethyl methacrylate blocks.

[0227] Synthesis Example 4 Synthesis of P(Sb-MMA)(45k-b-51k)

[0228] P(Sb-MMA)(45K-b-51K) was synthesized using the same procedure as described in Example 2. n As well as the composition of the PS and PMMA blocks, the amount of initiator and the amount of monomer were changed. In short, 20 g (0.192 mol) of styrene was polymerized with 0.32 mL (1.4 M solution) of sec-butyl lithium. Then 0.095 g (0.0005 mol) of 1,1'-diphenylethylene (DPE) in 2.5 ml of dry toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned into a dark brick red, indicating that the styrene lithium active center was converted into a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Methyl methacrylate (22.85 g, 0.23 mol) was then added via an ampoule. The reaction was terminated with 1 mL of degassed methanol after 30 minutes. The block copolymer was recovered by precipitation in excess isopropanol (5 times of the polymer solution) containing 10% water, filtering, and vacuum drying at 55°C for 12 hours to obtain 40 g of P(Sb-MMA) composed of 46.9 mol% polystyrene blocks and 53.1 mol% polymethyl methacrylate blocks (94% yield).

[0229] Equipped with and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first P(SDPE) block was n (GPC) = 45,048 g / mol and M w / M n =1.04. The molecular weight of the diblock copolymer obtained from GPC is M n,PS-b-PMMA=88,348 g / mol and M w / M n =1.02.

[0230] Synthesis Example 4a Synthesis of triblock polymer MMA-S-MMA, 50k-88k-50k

[0231] The triblock polymer MMA-S-MMA was prepared in THF solution using potassium naphthalene as an initiator using the procedure described in the literature (Makmrnol.Chem.191, 2309-2318 (1990) and Adv.Polym.Sci.86, 147 (1988)). In order to avoid the attack of the PS carbon anion on the ester group of MMA, 1,1-diphenylethylene (DPE) was introduced to reduce the nucleophilicity of the active site. In any case, the presence of a single DPE unit between the two blocks in the copolymer does not affect its performance. In order to carry out the polymerization of MMA under good conditions at low temperature (-70°C). The polymer prepared in this way has an Mw of PMMA (50K)-PS (88K)-PMMA (50K) measured by gel permeation color GPC, and a polydispersity of 1.04.

[0232] Synthesis Example 5: Synthesis of an oligomer of a statistical copolymer of styrene and methyl methacrylate (P(S-co-MMA)) for contact hole assembly additive

[0233] The reaction was carried out in a 250ml flask equipped with a condenser, a nitrogen inlet and a magnetic stirring bar under nitrogen. 18.23 grams (0.17mol) of styrene, 7.5 grams (0.075mol) of methyl methacrylate, 2 grams (0.012mol, 5% relative to total monomers) of azobisisobutyronitrile (AIBN) initiator, 0.7 grams (0.0075mol) of 1-butanethiol and 50 grams of anisole were loaded into the flask. The reaction solution was then degassed 3 times by vacuum / nitrogen circulation using a freeze-thaw method and finally filled with nitrogen. Then, the reaction was maintained in an oil bath at 85°C for 15 hours under stirring. Thereafter, the reaction solution was cooled to about 25°C. The reaction mixture was then diluted with 100mL of tetrahydrofuran and slowly poured into 700mL of isopropanol, mechanically stirred during the addition process. The precipitated polymer was collected by filtration. The collected polymer was dried at 40°C in a vacuum oven. The yield was 45%, and the M of the copolymer was 2.34 Å relative to the polystyrene calibration standard. n,GPC =4,700 g / mol, M w,GPC =6,500 g / mol, polydispersity index (PDI) is 1.38. Copolymer T g =86℃ and 1 H NMR confirmed that the copolymer had 63 mol % and 37 mol % of polystyrene and polymethyl methacrylate, respectively.

[0234] Synthesis Example 6: Synthesis of oligomers of statistical copolymers composed of styrene and methyl methacrylate (P(S-co-MMA)) for line and space assembly additives.

[0235] The reaction was carried out in a 250ml flask equipped with a condenser, a nitrogen inlet and a magnetic stirring bar under nitrogen. 13 grams (0.12 mol) of styrene, 13.7 grams (0.14 mol) of methyl methacrylate, 2 grams (0.012 mol, relative to 5% of total monomers) of azobisisobutyronitrile (AIBN) initiator, 0.7 grams (0.0075 mol) of 1-butanethiol and 50 grams of anisole were loaded into the flask. The reaction solution was then degassed 3 times by vacuum / nitrogen circulation using a freeze-thaw method and finally filled with nitrogen. Then, the reaction was maintained in an oil bath at 85°C for 15 hours under stirring. Thereafter, the reaction solution was cooled to about 25°C. The reaction mixture was then diluted with 100 mL of tetrahydrofuran and slowly poured into 700 mL of isopropanol, mechanically stirred during the addition process. The precipitated polymer was collected by filtration. The collected polymer was dried at 40°C in a vacuum oven. The yield was 45%, and the M of the copolymer was 2.34 Å relative to the polystyrene calibration standard. n,GPC =2,300 g / mol, M w,GPC =4,300 g / mol, polydispersity index (PDI) is 1.82. Copolymer T g =53℃ and 1 H NMR confirmed that the copolymer had 42 mol % and 58 mol % of polystyrene and polymethyl methacrylate, respectively.

[0236] Comparative Synthesis Example 1: Synthesis of a High Molecular Weight Statistical Copolymer of Styrene and Methyl Methacrylate (P(S-co-MMA)) for Line and Spacer Assembly Additives

[0237] For comparison purposes, a compound having M was also prepared in the absence of 1-butanethiol according to a procedure similar to that described in Synthesis Example 5. n 11,529, M w The higher molecular weight is 19,600K (PDI-1.7), with 45 mol% and 55 mol% of polystyrene and polymethyl methacrylate, respectively, in the copolymer. g It is a copolymer at 108°C.

[0238] Synthesis Example 7: Synthesis of an oligomeric block copolymer composed of styrene and methyl methacrylate for L / S assembly additives

[0239] The desired monomers were distilled into calibrated ampoules in the presence of a dehydrating agent and stored under N2. The liquid was transferred to the reactor via an ampoule or using a stainless steel cannula under N2. 400 mL of dry tetrahydrofuran was added to a dry 1L round-bottom reactor equipped with a side arm for connecting the ampoule, a magnetic stirring bar, and a nitrogen / vacuum three-way septum adapter. The temperature of the reactor was lowered to -78°C using a dry ice-acetone bath. Then, after titration of the impurities, 1.4 mL (0.00189 mol) of sec-butyl lithium was added to the reactor. Subsequently, styrene (18.8 g) was added to the reactor from an ampoule under rapid stirring. The reaction solution turned orange and the reaction was stirred for 10 minutes. Subsequently, 0.4 g of 1,1'-diphenylethylene (DPE) in 3 ml of anhydrous toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned into a deep brick red, indicating that the styrene lithium active center was converted to a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Then, 19.4 grams of methyl methacrylate (MMA) distilled with a small amount of triethylaluminum (1M in toluene) was added via an ampoule. The reaction was terminated after 15 minutes with 1 mL of degassed methanol. The block copolymer was recovered by precipitation in excess methanol (5 times the polymer solution) containing 10% water, filtered, and vacuum dried at 55°C for 12 hours to obtain 37 g of P (Sb-MMA) (97% yield).

[0240] Equipped with and Gel permeation chromatography (GPC) on a μ-ultrastyragel column showed that the M of the first PS block was n,PS (GPC) = 10,400 g / mol and M w / M n =1.06. The molecular weight of the diblock copolymer obtained from GPC is M n,P(S-b-MMA) =23,400 g / mol and M w / M n =1.09. Based on M n,PS The molecular weight of the PMMA block calculated by the NMR intensity of –OCH3 protons and aromatic protons is: n,PMMA (NMR) = 11,000 g / mol. This corresponds to V in the diblock copolymer. f-PS = 0.51. The triblock copolymer was also measured by GPC.

[0241] Synthesis Example 7a: Synthesis of an oligomeric block copolymer composed of styrene and methyl methacrylate for L / S assembly additives

[0242] This oligomeric block copolymer (Sb-MMA) (20K-23K) was synthesized in a manner similar to that described in Synthesis Example 7. The ratio of S-BuLi to monomer was adjusted to achieve the target molecular weight. and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first PS block was n,PS (GPC) = 20,253 g / mol and M w / M n =1.02. The molecular weight of the diblock copolymer obtained from GPC is M n , P(Sb-MMA)=41,098g / mol and M w / M n =1.02. The volume fraction determined by NMR is Vf-PS=0.506.

[0243] Synthesis Example 8: Synthesis of oligo(styrene-co-p-octylstyrene)-b-(methyl methacrylate-co-di(ethylene glycol) methyl ether methacrylate) for contact hole assembly additive

[0244] All monomers were distilled into calibrated ampoules in the presence of a dehydrating agent and stored under N2. The liquid was transferred to the reactor via an ampoule or using a stainless steel cannula under N2. 400 mL of dry tetrahydrofuran was added to a dry 1L round-bottom reactor equipped with a side arm for connecting the ampoule, a magnetic stirring bar, and a nitrogen / vacuum three-way septum adapter. The temperature of the reactor was lowered to -78°C using a dry ice-acetone bath. Then, after titration of the impurities, 1.2 mL (0.0016 mol) of sec-butyl lithium was added to the reactor. Subsequently, a mixture of styrene (8.92 g, S) and p-octyl styrene (3 g, OS) was added to the reactor from an ampoule under rapid stirring. The reaction solution turned orange-yellow and the reaction was stirred for 10 minutes. Subsequently, 0.35 g of 1,1'-diphenylethylene (DPE) in 2.5 ml of anhydrous toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned into a deep brick red, indicating that the styrene lithium active center was converted into a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Then, a mixture of methyl methacrylate (4.82 g, MMA) and di(ethylene glycol) methyl ether methacrylate (1.6 g, DEGMEMA) distilled with a small amount of triethylaluminum (1M in toluene solution) and CaH2, respectively, was added via an ampoule. After 15 minutes, the reaction was terminated with 1 mL of degassed methanol. The block copolymer was recovered by precipitation in an excess of methanol (5 times the polymer solution) containing 10% water, filtered, and vacuum dried at 55°C for 12 hours to obtain 17 g of oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) (94% yield), containing 25 mol% OS in the polystyrene block and 25 mol% DEGMEMA in the polymethyl methacrylate block. Equipped with and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first P(S-co-OS) block was n (GPC) = 13,000 g / mol and M w / M n =1.015. The molecular weight of the diblock copolymer obtained from GPC is M n,P(S-co-p-OS)-b-P(MMA-co-DEGMEMA) =19,500 g / mol and M w / M n = 1.04. The theoretical feed ratio of the nonpolar and polar blocks corresponds to V in the diblock copolymer. f-P(S-co-OS) =0.70. The block copolymer exhibits T g =79℃.

[0245] Synthesis Example 9: Synthesis of Oligo(Styrene-co-p-octylstyrene)-b-(Methyl Methacrylate-co-di(ethylene glycol)methyl ether methacrylate) (Oligomer(S-co-p-OS)-bP(MMA-co-DEGMEMA)) for L / S Assembly Additive

[0246] All monomers were distilled into calibrated ampoules in the presence of a dehydrating agent and stored under N2. The liquid was transferred to the reactor via an ampoule or using a stainless steel cannula under N2. 400 mL of dry tetrahydrofuran was added to a dry 1L round-bottom reactor equipped with a side arm for connecting the ampoule, a magnetic stirring bar, and a nitrogen / vacuum three-way septum adapter. The temperature of the reactor was lowered to -78 ° C using a dry ice-acetone bath. Then, after titration of the impurities, 1.0 mL (0.0013 mol) of sec-butyl lithium was added to the reactor. Subsequently, a mixture of styrene (10.64 g, S) and p-octyl styrene (1.76 g, OS) was added to the reactor from an ampoule under rapid stirring. The reaction solution turned orange-yellow and the reaction was stirred for 10 minutes. Subsequently, 0.32 g of 1,1'-diphenylethylene (DPE) in 2.5 ml of anhydrous toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned into a deep brick red, indicating that the styrene lithium active center was converted into a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Then, a mixture of methyl methacrylate (13.75 ml, 12.87 g, MMA) and di(ethylene glycol) methyl ether methacrylate (2 g, DEGMEMA) distilled with a small amount of triethylaluminum (1M toluene solution) and CaH2, respectively, was added via an ampoule. After 15 minutes, the reaction was terminated with 1 mL of degassed methanol. The block copolymer was recovered by precipitation in excess methanol (5 times the polymer solution) containing 10% water, filtered, and vacuum dried at 55°C for 12 hours to obtain 17 g of oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) (94% yield), containing 15 mol% OS in the polystyrene block and 14 mol% DEGMEMA in the polymethyl methacrylate block. Equipped with and Gel permeation chromatography using a μ-ultrastyragel column showed that the M of the first P(S-co-OS) block was n (GPC) = 10,800 g / mol and M w / M n =1.14. The molecular weight of the diblock copolymer obtained from GPC is M n,P(S-co-p-OS)-b-P(MMA-co-DEGMEMA) =30,000 g / mol and M w / M n= 1.07. The theoretical feed ratio of the nonpolar and polar blocks corresponds to V in the diblock copolymer. f-P(S-co-OS) =0.50. The block copolymer exhibits T g =90℃

[0247] Preparation Example 1-5 (Preparation Example 1-5)

[0248] Table 1 relates to the preparation of styrene and methyl methacrylate block copolymer P(Sb-MMA) for forming contact hole (CH) array. Preparations 1 to 5 are respectively free of additives (Formulation Example 1), oligomeric random copolymers containing styrene and methyl methacrylate (Formulation Examples 2 and 3) or containing oligomeric (styrene-co-p-octylstyrene)-b-(methyl methacrylate-co-di(ethylene glycol) methyl ether methacrylate) [oligomeric (P(S-co-p-OS)-bP(MMA-co-DEGMEMA))] (Formulations 4 and 5). These preparations are prepared by dissolving block copolymers P(Sb-MMA)(78k-39K)(Synthesis Example 2) and P(Sb-MMA)(34K-17K)(Synthesis Example 3) in propylene glycol methyl ether acetate (PGMEA) to form a 2.0wt% solution. These solutions are then combined and diluted to 1.5wt% using PGMEA. In Preparation Example 1, no additives are present, and the solution is then filtered using a PTFE membrane. For Formulations 2-5, the additives oligo(S-co-MMA) (Formulations 2 and 3) or oligo(S-co-p-OS)-bP(MMA-co-DEGMEMA) (Formulations 4 and 5) were added prior to filtration with the PTFE membrane as shown in Table 1.

[0249] Preparation Examples 6-9 and Comparative Preparations 1-3

[0250] Table 2 relates to the preparation of the block copolymer of styrene and methyl methacrylate P (Sb-MMA) for forming contact hole (CH) self-assembly.Preparation 6 to 9 is respectively free of additive (preparation example 6) or contains additive oligomeric (S-co-MMA) (preparation examples 7,8 and 9) or for comparative preparation examples 1 to 3, is the random high molecular weight copolymer P (MMA-co-S) [comparative preparation 1,2 and 3) containing styrene and methyl methacrylate. These preparations are prepared by dissolving the block copolymer P (Sb-MMA) (42K-47K) (synthesis example 4) of styrene and methyl methacrylate in PGMEA to form 2.0wt% solution.Then the solution is merged and PGMEA is diluted to 1.5wt%.In the preparation example 6 without additive, the solution is then filtered using PTFE membrane. For Formulation Examples 7 to 9 (Formulation Examples 7 to 9) or Comparative Examples 1 to 3 (Comparative Examples 1-9), before filtering with a PTFE membrane, additives oligomeric P(S-co-MMA) (Synthesis Example 9), high molecular weight random copolymer P(S-co-MMA) of styrene and methyl methacrylate (Comparative Synthesis Example 1) were added respectively, as shown in Table 2.

[0251] Preparation Examples 6, 10-14

[0252] Table 3 relates to the preparation of the block copolymer P (Sb-MMA) of styrene and methyl methacrylate for forming contact hole lines and interval (L / S) arrays.These preparations are prepared by dissolving the block copolymer P (Sb-MMA) (42K-47K) (Synthesis Example 4) of styrene and methyl methacrylate in PGMEA to form a solution of 2.0wt%.Then these solutions are merged and diluted to 1.5wt% using PGMEA.In the additive-free formulation example 6, the PTFE membrane filtration solution is then used.For formulation examples 10 to 12, (formulation examples 10 to 12) or for formulation examples 13 to 14, before filtering with PTFE membrane, the oligomeric block copolymers of additive oligomeric (S-co-p-OS)-bP (MMA-co-DEGMEMA), styrene and methyl methacrylate are added respectively (Sb-MMA), as shown in Table 3.

[0253] Preparation Examples 15, 16 and Comparative Preparation Example 4

[0254] Preparation of stock solutions

[0255] A first stock solution (3.2 wt%) of ABA triblock copolymer was prepared by dissolving 0.6 g of Synthesis Example 4a in 18 g of PGMEA and filtering the solution.

[0256] A second stock solution (3.2 wt %) of the oligomeric block copolymer of Synthesis Example 9 was prepared by dissolving 0.6 g of this material in 18 g of PGMEA and filtering the solution.

[0257] A third stock solution of the oligomeric block copolymer of Synthesis Example 7a was prepared by dissolving 0.83 g of this material in 25 g of PGMEA and filtering the solution.

[0258] Comparative Preparation Example 4

[0259] A first stock solution of just the triblock copolymer solution was used as Comparative Example 4 to establish the defect levels found during self-assembly of the triblock copolymer without the addition of an oligomeric additive component.

[0260] Preparation Example 15

[0261] This formulation was prepared by combining 4.6 g of the first stock solution containing Synthesis Example 4a with 0.92 g of the second stock solution. This solution was used to show the effect of component type 2-b) oligomeric block copolymers (Synthesis Example 9) on the defect levels found during the self-assembly of triblock copolymers.

[0262] Preparation Example 16

[0263] This formulation was prepared by combining 5.4 g of the first stock solution containing Synthesis Example 4a with 1.08 g of the second stock solution. This solution was used to show the effect of component type 3-b) oligomeric block copolymer (Synthesis Example 4a) on the defect levels found during the self-assembly of the triblock copolymer.

[0264] Treatments of Comparative Example 4, Formulation Example 15, and Formulation Example 16.

[0265] The formulations were filtered through a 0.2 μm Teflon filter before coating. Coating was performed using a TEL ACT 8 track on 8" silicon wafers pre-coated with a neutral layer (see below), followed by a soft bake at 110°C for 1 minute and a hard bake at 250°C for 1 hour.

[0266] Neutral Layer

[0267] For all block copolymer formulations tested, silicon wafers were first coated with a neutral layer formulation (Neutral Layer Formulation 1) prepared by dissolving the polymer of Synthesis Example 1 into PGMEA to form a neutral layer formulation for coating the overcoated wafers as follows: a neutral layer was formed by casting Neutral Formulation Example 1 (74% PS) on a silicon wafer and baking at 240°C / 5 minutes, followed by rinsing with PGMEA for 30 seconds and baking at 110°C for 1 minute.

[0268] Processing of self-assembled films

[0269] Unless otherwise stated, the formulations described herein for self-assembly were spun at 1500 rpm on top of the neutral layer to form a film with a thickness of 50 nm, and then baked at 250° C. for 5 minutes under nitrogen to affect self-assembly. After self-assembly, the films were then etched with oxygen plasma for a time between 0 and 70 seconds, as shown in the specific figures and tables herein. Oxygen etching was performed using a Norsdson March etcher, RF power = 50 (W), base pressure = 50 (mTorr), process pressure = 90 (mTorr), O2 = 15 (sccm).

[0270] Self-assembly and etching results

[0271] CH preparation results

[0272] As shown in the examples in Table 1, formulations of blend P(Sb-MMA) polymers containing up to 30 wt% of oligomeric additives showed up to 3 times fewer defects seen after oxygen plasma etching compared to reference samples without these additives.

[0273] Specifically, Figure 1 Top-down SEM studies (2 μm FOV) of self-organization and etching of CH block copolymer formulations of poly(styrene-block-methyl methacrylate) [blends of P(Sb-MMA) (78K-b-39K) and ((34K-b-17K)] as described in Table 1 when cast as films on a neutral layer are shown. These results illustrate the effect of adding 0 to 20 wt% of the additive oligomeric (S-co-MMA) in 50 nm films (~1 Lo) of these formulations when coated on a neutral layer, annealed at 250°C to induce self-assembly, and then etched. The films were etched with oxygen plasma for 50 or 70 seconds. The number of defects observed in these etched self-assembled films decreased greatly with increasing loading of this oligomeric additive. In contrast, formulations without this additive showed a greater number of defects.

[0274] Similarly, Figure 2 An x-section SEM view (250 magnification) of the self-assembled film of the CH formulation after etching for 20 seconds is shown, where the number of defects decreases as the loading of the additive increases from 10 wt % to 20 wt %.

[0275] Figure 3 Shows a similar Figure 1Top-down SEM CH defects of the study discussed. However, in this case, the additive used was oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) [Synthesis Example 8] instead of oligomeric (S-co-MMA). It was also found that with oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA), the number of defects observed was greatly reduced as the loading increased from 0wt% to 20wt%, as shown in Figure 3 shown.

[0276] L / S preparation results

[0277] Figure 4 Shown is a top-down SEM L / S study of self-assembled films of block copolymer P(Sb-MMA)(45.4kb-51k) without oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) or with 10, 20 or 30 wt% of the additive [Synthesis Example 9] when cast on a neutral layer. These formulations are formulations 6, 7, 8 and 9 in Table 3, respectively. After these self-assembled films were etched with oxygen plasma for 30, 50 or 70 seconds, the samples without the additive showed a large number of defects, while in contrast, the samples with 10 wt% or 20 wt% of the additive showed almost no defects even after etching for 70 seconds.

[0278] Figure 5 Shown is a top-down SEM L / S study of self-assembled films of block copolymer P(Sb-MMA)(45.4kb-51k) formulated without (also referred to as 0 wt%) or with such an additive [Synthesis Example 7] of oligo(Sb-MMA) (10 or 20 wt%) when cast on a neutral layer. These formulations are formulations 6 (0 wt%), 13 (10 wt%) and 14 (20 wt%) in Table 3, respectively. After these self-assembled films were etched with oxygen plasma for 30 seconds, the samples without the additive (0 wt%) showed a large number of defects, while in contrast, the samples with 10 wt% or 20 wt% of the additive showed no obvious defects even after etching for 30 seconds.

[0279] Tables 4 and 5 summarize the defect results obtained for the L / S formulations described in Table 2 after self-assembly and etching. Tables 4 and 5 compare the defect results of the L / S formulations containing low T in the range of 10 wt% to 30 wt% loading after self-assembly and oxygen plasma etching, respectively. g The films cast on the neutral layer of the block copolymer P(Sb-MMA)(45.4kb-51k) (Formulations 7, 8 and 9) containing the same amount of additive oligo(S-co-MMA) [Synthesis Example 6] were compared with the films cast on the neutral layer of the block copolymer P(Sb-MMA)(45.4kb-51k) containing the same amount of additive oligo(S-co-MMA) [Synthesis Example 6] gThe defect results obtained for films cast from formulations containing the high molecular weight additive P(S-co-MMA) [Comparative Synthesis Example 1] (Comparative Formulations 1, 2 and 3) are compared. This unexpectedly shows that oligo(S-co-MMA) [Synthesis Example 7] gives lower average number of network assembly defects per square micron (def / μm) than formulations containing P(S-co-MMA) [Comparative Synthesis Example 1]. 2 ).

[0280] Figure 6 Shown are top-down SEM L / S studies of self-assembled films of block copolymers P(MMA-bSb-MMA) (50k-88k-50k) formulated without additive (also referred to as 0 wt%), with such additive of oligomeric (S-co-p-OS)-bP(MMA-co-DEGMEMA) (20 wt%) [Synthesis Example 9], or with such additive of oligomeric (Sb-MMA) (20 wt%) [Synthesis Example 7a] when cast on a neutral layer. These last two formulations are formulations 15 (20 wt%) and 16 (20 wt%) in Table 3, respectively. After these self-assembled films were etched with oxygen plasma for 30 seconds. The number of defects of these 3Lo FT self-assembled films with 3L0 was obtained using Hitachi DSA APPS software. The sample without additives (0 wt%) showed a large number of defects (101 defects), while in contrast, the samples with 20 wt % (oligo(S-co-p-OS)-bP(MMA-co-DEGMEMA) or 20 wt % oligo(Sb-MMA) showed defect levels of only 7 and 15, respectively.

[0281]

[0282]

[0283]

[0284] Table 4

[0285] Defect results of P(Sb-MMA) (45.4kb-51k) formulations with or without additive oligo(S-co-MMA)

[0286]

[0287] Table 5

[0288] Defective results of P(Sb-MMA)(45.4kb-51k) formulations with and without high molecular weight (19.6K) P(S-co-MMA)

[0289]

Claims

1. A composition comprising components a), b) and c), wherein a) is a block copolymer component or a blend of at least two block copolymers, b) is a low T copolymer selected from the group consisting of oligomeric random copolymers b-1), oligomeric diblock copolymers b-2), oligomeric diblock copolymers b-3) and mixtures thereof. g Additives, including b-1) is an oligomeric random copolymer having two repeating units of structure (Ib) and structure (IIb), wherein R 1b and R 2b is H and R 3b and R 4b is a methyl group, and Based on the total moles of the repeating units of structures (Ib) and (IIb), the mole % value of the repeating unit of structure (Ib) is 40 to 80 mole %, and the mole % value of the repeating unit of structure (IIb) is 20 to 60 mole %, and wherein the individual values ​​of the mole % of repeating units of structures (Ib) and (IIb) are selected from their respective ranges so that the total number of moles of repeating units of structures (Ib) and (IIb) adds up to 100 mole %; and further The oligomeric random copolymer b-1) has a T g 0℃ to 80℃, M n is 1000 g / mol to 5000 g / mol, and the polydispersity is 1.3 to 1.5, b-2) is an oligomeric diblock copolymer of block Ab) and block Bb), wherein M n is from 15,000 to 32,000 and the polydispersity is from 1.03 to 1.08, wherein Block Ab) is a random copolymer having repeating units of structures (III) and (IV), and block Bb) is a random copolymer having repeating units of structures (V) and (VI), and R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, wherein R6 is n-octyl, R8 is C-1 to C-4 alkyl, R 10 is methyl, R 12 and R 13 is ethylene, and R 14 is methyl, and the oligomeric diblock copolymer b-2) has a T g The value is 0℃ to 95℃, and b-3) is an oligomeric diblock copolymer of blocks Ac) having repeating units of structure (Ic) and blocks Bc) having repeating units of structure (IIc), wherein R 1c and R 2c For H, R 3c and R 4c is a methyl group, and Based on the total moles of repeating units of structures (Ic) and (IIc), the mole % value of repeating units of structure (Ic) is 36 mole % to 74 mole % and the mole % value of repeating units of structure (IIc) is 26 mole % to 64 mole %, and the respective values ​​of the mole % of repeating units of structures (Ic) and (IIc) are selected from their respective ranges so that the total moles of repeating units of structures (Ic) and (IIc) add up to 100 mole %; and The oligomeric diblock copolymer b-3) has an M n is 15000 g / mol to 30000 g / mol, the polydispersity is 1.02 to 1.08 and T g 0℃ to 115℃, c) is spin casting of organic solvents.

2. The composition of claim 1, wherein the component a) is selected from a single triblock copolymer and a blend of at least two triblock copolymers, or a single diblock copolymer and a blend of at least two diblock copolymers.

3. The composition of claim 1 or 2, wherein the component a) is an ABA triblock copolymer component selected from the group consisting of an ABA triblock copolymer a-1t), an ABA triblock copolymer a-2t), and a blend of an ABA triblock copolymer a-1t) and an ABA triblock copolymer a-2t), wherein a-1t) is an ABA triblock copolymer comprising an intermediate B) styrene block segment having repeating units of styrene structure (I) and two terminal acrylic block A) segments of equal length having structure (II), wherein R1 and R3 are independently selected from H and C-1 to C-4 alkyl, R2 is H or C-1 to C-8 alkyl, R4 is C-1 to C-8 alkyl, and Based on the total moles of the repeating units of structures (I) and (II), the mole % value of the repeating unit of structure (I) is 40 to 80 mole %, and the mole % value of the repeating unit of structure (II) is 20 to 60 mole %, wherein the individual values ​​of the mole % of the repeating units of structures (I) and (II) are selected from their respective ranges such that the total number of moles of the repeating units of structures (I) and (II) adds up to 100 mole %, and The polydispersity of the triblock copolymer a-1t) is 1.0 to 1.1, and M n 70,000 g / mol to 350,000 g / mol, a-2t) is an ABA triblock copolymer comprising a middle B) block segment having repeating units of a styrene structure (Ia) and two end B) blocks of equal length having an acrylic structure (IIa), wherein R 1a and R 3a are independently selected from H and C-1 to C-4 alkyl, R 2a is H or C-1 to C-8 alkyl, R 4a is a C-1 to C-8 alkyl group, Based on the total moles of the repeating units of structures (Ia) and (IIa), the mole % value of the repeating unit of structure (Ia) is 40 to 80 mol %, and the mole % value of the repeating unit of structure (IIa) is 20 to 60 mol %, and wherein the individual values ​​of the mole % of repeating units of structures (Ia) and (IIa) are selected from their respective ranges so that the total number of moles of repeating units of structures (Ia) and (IIa) adds up to 100 mole %, and The polydispersity of the triblock copolymer a-2t) is 1.0 to 1.1, and M n 70,000 g / mol to 350,000 g / mol, 4. The composition of claim 3, wherein R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a It's methyl.

5. The composition of claim 1, wherein component a) is a triblock copolymer selected from the group consisting of a triblock copolymer of structure (ABA-1), a triblock copolymer of structure (ABA-2), and a mixture of these two block copolymers, wherein mt, mta, nt, and nta are the number of repeating units, R 1s , R 1sa , R 2s and R 2sa independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s and Si(R 5s )3, where R 3s , R 4s and R 5s independently selected from C-1 to C-4 alkyl, 6. The composition of claim 5, wherein R1, R 1a , R2, R 2a and R 1s and R 2s is H and R3, R 3a , R4 and R 4a It's methyl.

7. The composition of claim 1 or 2, wherein a) is a diblock copolymer component selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2), and blends of a-1) and a-2), wherein a-1) is a diblock copolymer of a block A) of styrene repeating units having a styrene structure (I) and a block B) having an acrylic structure (II), wherein R1 and R3 are independently selected from H and C-1 to C-4 alkyl, R2 is H or C-1 to C-8 alkyl, R4 is C-1 to C-8 alkyl, and Based on the total moles of the repeating units of structures (I) and (II), the mole % value of the repeating unit of structure (I) is 40 to 80 mole % and the mole % value of the repeating unit of structure (II) is 20 to 60 mole %, wherein the individual values ​​of the mole % of the repeating units of structures (I) and (II) are selected from their respective ranges such that the total number of moles of the repeating units of structures (I) and (II) adds up to 100 mole %, and The polydispersity of the diblock copolymer a-1) is from 1.0 to 1.1 and M n 50,000 g / mol to 150,000 g / mol, a-2) is a diblock copolymer of a block Aa) having a repeating unit of a styrene structure (Ia) and a block Ba) having a repeating unit of an acrylic acid structure (IIa), wherein R 1a and R 3a are independently selected from H or C-1 to C-4 alkyl, R 2a is H or C-1 to C-8 alkyl, C 4a is a C-1 to C-8 alkyl group, and The mole % value of the repeating unit of structure (Ia) is 40 mol % to 80 mol % and the mole % value of the repeating unit of structure (IIa) is 20 mol % to 60 mol % based on the total moles of the repeating units of structures (Ia) and (IIa), and wherein the individual values ​​of the mole % of repeating units of structures (Ia) and (IIa) are selected from their respective ranges so that the total number of moles of repeating units of structures (Ia) and (IIa) adds up to 100 mole %, and The polydispersity of the diblock copolymer a-2) is from 1.0 to 1.1 and M n 30,000 g / mol to 90,000 g / mol, 8. The composition of claim 6, wherein component a) is wherein R1, R 1a , R2 and R 2a is H and R3, R 3a , R4 and R 4a It is the methyl component a).

9. The composition of claim 7, wherein the diblock copolymers a-1) and a-2) have structures (IS) and (ISa), respectively, wherein R 1s , R 1sa , R 2s and R 2sa independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s and Si(R 5s )3, where R 3s , R 4s and R 5s independently selected from C-1 to C-4 alkyl, 10. The composition of claim 9, wherein R 1s , R 2s , R 1sa and R 2sa It's hydrogen.

11. The composition of claim 1, wherein the oligomeric diblock copolymer components b-2) and b-3) have a spacer between block Ab) and block Bb) or between block Ac) and block Bc), respectively, as shown in Structure (ISb) and Structure (ISc), respectively, wherein R 1sb , R 1sc , R 2sb and R 2sc independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s 、Si(R 5s )3, where R 3s , R 4s and R 5s independently selected from C-1 to C-4 alkyl, 12. The composition of claim 11, wherein R 1sb , R 2sb , R 1sc and R 2sc It's hydrogen.

13. The composition of claim 1 wherein the polydispersity of the diblock copolymer component a-1) is from 1.00 to 1.03 for component a).

14. The composition of claim 1, wherein for component a), the M of the diblock copolymer component a-1) is n It is 93,000 g / mol to 105,300 g / mol.

15. The composition of claim 1, wherein for component a), in the diblock copolymer component a-1), the mole % value of repeating units of structure (I) is 40 to 60 mole %, and the mole % value of repeating units of structure (II) is 40 to 60 mole %.

16. The composition of claim 1, wherein for component a), the mole % value of the repeating unit of structure (I) in the diblock copolymer component a-1) is 60 mole % to 75 mole % and the mole % value of the repeating unit of structure (II) is 25 mole % to 40 mole %.

17. The composition of claim 1 wherein the polydispersity of the diblock copolymer component a-2) is from 1.00 to 1.03 for component a).

18. The composition of claim 1, wherein for component a), the M of the diblock copolymer component a-2) is n 40,800 g / mol to 61,200 g / mol.

19. The composition of claim 1, wherein for component a), in a single block copolymer a-1) or a-2) or a blend of a-1) and a-2), the total mole % value of repeating units of structures (I) and (Ia) is 40 to 60 mole % and the total mole % value of repeating units of structures (II) and (IIa) is 40 to 60 mole %.

20. The composition of claim 1, wherein for component a), in a single block copolymer a-1) or a-2) or a blend of a-1) and a-2), the total mole % value of repeating units of structures (I) and (Ia) is 60 to 75 mole % and the total mole % value of repeating units of structures (II) and (IIa) is 25 to 40 mole %.

21. The composition of claim 1, wherein component a) is a blend of a-1) and a-2).

22. The composition of claim 1, wherein component a) is a-1) or a-2).

23. The composition of claim 1, wherein component a) is from 0.5 wt% to 2.0 wt% of the total composition.

24. The composition of claim 1, wherein for component b), the oligomeric random copolymer b-1) has a T g 50℃ to 90℃.

25. The composition of claim 1, wherein component b) is an oligomeric random copolymer b-1).

26. The composition of claim 1, wherein for component b), the oligomeric diblock copolymer b-2) is wherein R5, R7 and R8 are H, R6 is n-octyl or n-nonyl, R9 and R 11 is methyl, R 10 is methyl or ethyl, R 12 and R 13 are independently ethylene or propylene, and R 14 It is a methyl or ethyl oligomeric diblock copolymer.

27. The composition of claim 1, wherein for component b), the oligomeric diblock copolymer b-2) is an oligomeric diblock copolymer wherein the mole % of repeating units of structure (IV) is 25 mole % to 50 mole % and the mole % of repeating units of structure (V) is 40 mole % to 60 mole %.

28. The composition of claim 1, wherein for component b), the oligomeric diblock copolymer b-2) is an oligomeric diblock copolymer wherein the mole % of repeating units of structure (III) is 20% to 30% of the mole % of repeating units of structure (IV), and the mole % of repeating units of structure (VI) is 12% to 20% of the mole % of repeating units of structure (V).

29. The composition of claim 1, wherein for component b), the oligomeric diblock copolymer b-2) has a T g 50℃ to 90℃.

30. The composition of claim 1 wherein component b) is an oligomeric diblock copolymer b-2).

31. The composition of claim 1, wherein component b) is an oligomeric diblock copolymer b-3), and is an oligomeric diblock copolymer wherein the mole % of repeating units of structure (Ic) is from 40 to 70 mole % and the mole % of repeating units of structure (IIc) is from 40 to 70 mole %.

32. The composition of claim 1, wherein for component b), the oligomeric diblock copolymer b-3) has a T g 50℃ to 90℃.

33. The composition of claim 1 wherein component b) is a diblock copolymer b-3).

34. The composition of claim 1, wherein component a) is a diblock copolymer component selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2) and blends of a-1) and a-2), the total mole % of styrene repeating units of structures (I) and (Ia) of which is 60 to 75 mole % and the total mole % of acrylic repeating units of structures (II) and (IIa) of which is 40 to 60 mole %, and component b) is copolymer b-1), oligomeric diblock copolymer b-2) or copolymer b-3).

35. The composition of claim 1, wherein component a) is a diblock copolymer component selected from the group consisting of diblock copolymers a-1), diblock copolymers a-2) and blends of a-1) and a-2), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is from 60 to 75 mole %, and further wherein the total mole % of acrylic repeating units of structures (II) and (IIa) is from 25 to 40 mole %, and component b) is an oligomeric random copolymer b-1), an oligomeric diblock copolymer b-2) or an oligomeric diblock copolymer b-3).

36. The composition of claim 1, wherein component a) is selected from the group consisting of triblock copolymer component a-1t), triblock copolymer a-2t) and blends of a-1t) and a-2t), the total mole % of styrene repeating units of structures (I) and (Ia) of which is 60 to 75 mole % and the total mole % of acrylic repeating units of structures (II) and (IIa) of which is 40 to 60 mole %, and component b) is copolymer b-2 or oligomeric diblock copolymer b-3).

37. The composition of claim 1, wherein component a) is selected from the group consisting of triblock copolymer component a-1t), triblock copolymer a-2t) and blends of a-1t) and a-2t), wherein the total mole % of styrene repeating units of structures (I) and (Ia) is 60 to 75 mole %, and further wherein the total mole % of acrylic repeating units of structures (II) and (IIa) is 25 to 40 mole %, and component b) is an oligomeric diblock copolymer b-2) or an oligomeric diblock copolymer b-3).

38. A method comprising the steps of: i) forming a coating of a neutral layer on a substrate, ii) applying the composition according to any one of claims 1 to 35 onto the neutral layer to form a film, ii) baking the film at a temperature selected from 240° C. to 260° C. in an inert gas atmosphere to form a self-assembled film, and iii) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

39. A method of forming a line and space array comprising the steps of: ia) forming a coating of a neutral layer on a substrate, iia) applying the composition according to claim 34 onto the neutral layer to form a film, iiia) baking the film at a temperature selected from 240° C. to 260° C. in an inert gas atmosphere to form a self-assembled film, and iva) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

40. A method for forming a contact hole array, comprising the following steps: ib) forming a coating of a neutral layer on a substrate, iib) applying the composition according to claim 35 onto the neutral layer to form a film, iiib) baking the film at a temperature selected from 240° C. to 260° C. in an inert gas atmosphere to form a self-assembled film, and ivb) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

41. A method of forming a line and space array comprising the steps of: ic) forming a coating of a neutral layer on a substrate, iiic) applying the composition of claim 36 onto the neutral layer to form a film, ivc) baking the film at a temperature selected from 240° C. to 260° C. in an inert gas atmosphere to form a self-assembled film, and vc) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

42. A method for forming a contact hole array, comprising the following steps: id) forming a coating of a neutral layer on a substrate, iiid) applying the composition according to claim 37 onto the neutral layer to form a film, ivd) baking the film at a temperature selected from 240° C. to 260° C. in an inert gas atmosphere to form a self-assembled film, and vd) etching the substrate with plasma to transfer the self-assembled film pattern into the substrate.

43. An oligomeric diblock copolymer comprising a block Ab) and a block Bb), wherein M n The molecular weight of the present invention is 1,000 to 35,000 g / mol and the polydispersity is 1.0 to 1.1, wherein block Ab) is a random copolymer having repeating units of structures (III) and (IV), and block Bb) is a random copolymer having repeating units of structures (V) and (VI), and R5, R7, R9 and R 11 independently selected from H or C-1 to C-4 alkyl, R6 is C-7 to C-10 straight chain alkyl, R8 is C-1 to C-4 alkyl, R 10 is a C-1 to C-4 alkyl group, R 12 and R 13 are each selected from C-2 to C-5 alkylene, and R 14 is a C-1 to C-4 alkyl group, and the T g The value is 0℃ to 95℃, 44. The oligomeric diblock copolymer of claim 43, wherein the oligomeric diblock copolymer has a spacer between block Ab) and block Bb), as shown in structure (ISb), wherein R 1sb and R 2sb independently selected from hydrogen, C-1 to C-8 alkyl, -N(R 3s )2.-OR 4s 、Si(R 5s )3, where R 3s , R 4s and R 5s independently selected from C-1 to C-4 alkyl, 45. The oligomeric diblock copolymer of claim 44, wherein R 1sb and R 2sb It's hydrogen.

46. ​​The oligomeric diblock copolymer of claim 43, wherein R5, R7 and R8 are H, R6 is a C-8 to C-9 straight chain alkyl, R9 and R 11 is methyl, R 10 is methyl or ethyl, R 12 and R 13 are independently ethylene or propylene, and R 14 It is methyl or ethyl.

47. The oligomeric diblock copolymer of claim 43, wherein the oligomeric diblock copolymer is wherein R6 is n-octyl, R 10 is methyl, R 12 and R 13 is ethylene, and R 14 It is a methyl oligomeric diblock copolymer.

48. The oligomeric diblock copolymer of claim 43, wherein the mole % of the sum of the mole % of repeating units (III) and (IV) is from 40 mole % to 80 mole % and the mole % of repeating units (V) and (VI) is in the range of 20 mole % to 60 mole %, based on the total moles of repeating units having structures (III), (IV), (V) and (VI), and further, wherein the mole % of repeating units (III) is in the range of 2 mole % to 80 mole % and the mole % of repeating units (VI) is in the range of 1 mole % to 80 mole %, and further, wherein the individual values ​​of the mole % of repeating units of structures (III), (IV), (V) and (VI) are selected from their respective ranges such that the total moles of repeating units of structures (III), (IV), (V) and (VI) add up to 100 mole %.

49. The oligomeric diblock copolymer of claim 43, wherein the mole % of repeating unit (III) is from 2 mole % to 64 mole %.

50. The oligomeric diblock copolymer of claim 43, wherein the mol% of (VI) is in the range of 2 mol% to 48 mol%.

51. The oligomeric diblock copolymer of claim 43, wherein the oligomeric diblock copolymer is an oligomeric diblock copolymer wherein the mole % of repeating units of structure (IV) is from 25 mole % to 50 mole % and the mole % of repeating units of structure (V) is from 40 mole % to 60 mole %.

52. The oligomeric diblock copolymer of claim 44, wherein the oligomeric diblock copolymer has a polydispersity of 1.03 to 1.

08.

53. The oligomeric diblock copolymer of claim 44, wherein the M of the oligomeric diblock copolymer is n 15,000 g / mol to 32,000 g / mol.

54. The oligomeric diblock copolymer of claim 44, wherein the oligomeric diblock copolymer has a T g 50℃ to 90℃.

55. Use of a composition according to any one of claims 1 to 37 or an oligomeric diblock copolymer according to any one of claims 43 to 54 for the preparation of a self-assembled film on a substrate.

Citation Information

Patent Citations

  • Process for controlling the period characterizing the morphology obtained from a blend of block copolymers and of co(polymers) of one of the blocks

    US20150030971A1

  • Copolymer formulation for directed self assembly, methods of manufacture thereof and articles comprising the same

    US20160186001A1